Total plasma N-glycomic patterns of COVID-19 disease - Georgia Elgood-Hunt; Jack Cheeseman; Richard A. Gardner; Thomas Sénard; Paulina A. Urbanowicz; Alejandro A. Garcia Leon; Cormac McCarthy; Marco P. Monopoli; Daryl L. Fernandes; Craig P. Thompson; Oleg A. Mayboroda; Patrick. W.G. Mallon; et al. (Glycoconjugate Journal, 2026)
Total plasma N -glycans alter in disease states, with few studies focused on COVID-19. A discovery cohort of 310 COVID-19 patients, replicated with 97 COVID-19 patients and tested with 100 COVID-19 patients, was used to unearth the N -glycans capable of distinguishing infection, as well as prognosis of intensive care unit (ICU) admission and mortality. All significant bisected glycans were decreased in patients compared to controls, whilst fucosylated tri-antennary glycans and sialylated tetra-antennary glycans were increased in patients. For both those admitted to the ICU and those who died, Peak 61 (A4G4S4F) was elevated in the more severe disease course, while Peak 29 (FA2G2S2) was lowered. Pinpointing specific glycosylation changes has alluded to a potential story of glycoprotein pathways in response to SARS-CoV-2 infection. This study could be further explored through deriving the glycoproteins associated with the glycans of interest and the glycosylation changes experienced on these proteins. Graphical Abstract

Bridging soil mapping units and digital soil mapping through probability-driven machine learning: an uncertainty-aware framework for soil class prediction in Antarctica - Rafael G. Siqueira; Cássio M. Moquedace; Márcio R. Francelino; Carlos Ernesto G.R. Schaefer; Roberto F.M. Michel; Daniela Schmitz; Flávia R. Ferrari; Caroline Delpupo; Eduardo O. Senra; Heitor P. Palma; Daniel N. Krum; Fábio S. de Oliveira; et al. (CATENA, 2026)

Integrated control of Rhipicephalus microplus: Assessment of the use of chemical acaricides and Metarhizium anisopliae in cattle from a tropical climate region - Evandro Davanco Ferreira de Souza; Vanessa Ferreira Salvador; Luccas Lourenzzo Lima Lins Leal; Igor Maciel Lopes de Morais; Rafael Assunção de Carvalho; Harthur Amoury Ferreira Lima; Haile Dean Figueiredo Chagas; Andreas Lemes Seabra; Marcus Antonio Martins Buso; Lorena Lopes Ferreira; Éverton Kort Kamp Fernandes; Caio Marcio de Oliveira Monteiro; et al. (Veterinary Parasitology, 2026)

Biodegradation of Diuron By Indigenous Soil Bacteria Isolated From Herbicide-contaminated Sites - Kadidja Ianne do Vale Almeida; Paulo Sérgio Fernandes das Chagas; Caio Álisson Diniz da Silva; Victória Késsia Silva Araújo; Bianca Pietra Santos Diniz; Francisco Sérvulo de Oliveira Carvalho; Jarlan Lucas dos Santos Silva; Ana Lara Alves Ferreira Landim; Luiz Fernando de Sousa Antunes; Caio Augusto Martins Aires; Rafael Wesley Bastos; Marcia Michelle de Queiroz Ambrosio; et al. (Water, Air, & Soil Pollution, 2026)
Residual herbicides are widely used in weed management; however, their persistence in the environment can lead to agronomic and ecological impacts. This study assessed bacterial isolates obtained from sugarcane soil with a history of diuron exposure for their ability to increase diuron dissipation under controlled conditions. Forty-two bacterial isolates were obtained, of which 18 tolerated the commercial formulation at 1,000 mg L −1 . In vitro assays identified isolates 7, 10, and 40 as the highest-performing isolates, with diuron reductions of 47.49%, 46.39%, and 43.86%, respectively. In autoclaved-soil microcosms, total diuron dissipation after 42 days reached 65.89%, 65.30%, and 65.81% for isolates 3, 7, and 35, respectively, compared with 52.91% in the uninoculated control; these values correspond to absolute increases of 12.98, 12.39, and 12.90 percentage points above the control. The estimated half-life decreased from 40.41 days in the control to 22.14, 22.60, and 22.29 days for isolates 3, 7, and 35, respectively. DCPMU (3-(3,4-dichlorophenyl)-1-methylurea) and DCA (3,4-dichloroaniline) were detected during incubation. The higher DCPMU levels are consistent with an initial N-demethylation step, whereas DCA was detected mainly at later sampling times and was not consistently increased by inoculation. Thus, the data support diuron transformation and increased dissipation but do not demonstrate complete degradation, mineralization, or detoxification. MALDI-TOF MS protein profiling provided provisional taxonomic matches for the selected isolates; no sequence-based confirmation was performed. The findings identify numbered isolates for further controlled evaluation, while sequence confirmation, biosafety assessment, metabolite-fate studies, and validation in non-sterile soil are required before any applied use.

Unveiling the Viral Landscape in Gastric Cancer - Diego Pereira; Fabiano Cordeiro Moreira; Daniel de Souza Avelar; Sérgio Augusto Antunes Ramos; Valéria Cristiane Santos da Silva; Jéssica Manoelli Costa da Silva; Ronald Matheus da Silva Mourão; Rubem Ferreira da Silva; Kauê Sant’Ana Pereira Guimarães; Juliana Barreto Albuquerque Pinto; Marcos da Conceição; Williams Fernandes Barra; et al. (Current Microbiology, 2026)
The present study aimed to comprehensively characterize the cancer-associated virome in patients with gastric cancer. A total of 452 samples were analyzed, including 226 tumor tissues and 202 peritumoral tissues from patients undergoing surgical resection, alongside 24 normal gastric mucosa samples obtained via endoscopy from individuals without cancer. RNA was extracted, libraries were prepared, and paired-end sequencing was performed on the NextSeq 500 platform (Illumina, US). High-quality reads were processed with Kraken2, using the standard database supplemented with the Reference Viral Database, to identify viral taxa. Taxonomic profiles, differential viral abundance, and alpha and beta diversity metrics were computed in RStudio, with statistical analyses performed to compare viral composition and diversity among tissue groups using Kruskal-Wallis, Wilcoxon, PERMANOVA, and PERMDISP tests ( p

Partitioning and transformation of diuron in water–sediment systems: Influence of Eichhornia crassipes on contaminant redistribution and metabolite formation - Maria Carolina Ramírez Hernandez; Mateus Alencar Bezerra Silva; Matheus Alves Ribeiro; Breno De Holanda Almeida; Luiz Gustavo Alves De Alcântara; Bruno Caio Chaves Fernandes; Márcia Michelle De Queiroz Ambrósio; Paulo Sergio Fernandes Das Chagas; Claudinei Da Cruz; Daniel Valadão Silva (Journal of Hazardous Materials, 2026)

Degradation of diclosulam in water by corona plasma: role of reactive oxygen and nitrogen species - Andressa Germana de Souza; Taliane Maria da Silva Teófilo; Bruno Caio Chaves Fernandes; Frederico Ribeiro do Carmo; Jussier de Oliveira Vitoriano; Clodomiro Alves Júnior; Késia Kelly Vieira de Castro; Lucrecia Pacheco Batista; Caio Álisson Diniz da Silva; Gabriel Teles Santos da Silva; Jesley Nogueira Bandeira; Daniel Valadão Silva; et al. (Journal of Environmental Management, 2026)

High-altitude Amazonian eukaryotic shells (Arcellinida, Amoebozoa) - João P.B. Alcino; Maria Beatriz Gomes e Souza; Denilson Fernandes Peralta; Daniel J.G. Lahr (European Journal of Protistology, 2026)

Bisphenol A alternatives (BPS and BPAF) disrupt anti-predatory behavior and intergenerational behavioral responses in zebrafish (Danio rerio) - Daniel Fernandes da Costa; Gustavo Venâncio da Silva; Marina Sanson Bellot; Hamid R. Habibi; Rafael Henrique Nóbrega; Percilia Cardoso Giaquinto (Aquatic Toxicology, 2026)

Adverse effects posed by phthalates in marine mussels: Metabolism of phase I and II, antioxidant defense and peroxidative damage - Ana Margarida Costa; Ana Catarina Fernandes; David Daniel; Bruno Nunes (Aquatic Toxicology, 2026)

Field measurements reveal local limits of imputed functional traits in tropical trees - Wénita de Souza Justino; Daniel Negreiros; Lara Rodrigues de Andrade; Ilana Zanoni; Miriam Cristina Alvarez Pereira; Simon Pierce; Geraldo Wilson Fernandes (Plant Ecology, 2026)
This study evaluated the reliability of functional data imputed in the classification of ecological strategies according to the CSR model (competitive, stress-tolerant, ruderal) in tree species of a riparian Atlantic Forest in Brazil. Empirical data collected in situ from 68 species were compared with data imputed using the Bayesian Hierarchical Probabilistic Matrix Factorization (BHPMF) technique, considering key functional attributes such as leaf area and specific leaf area. The results showed significant divergences between the classifications based on measured and imputed data, especially for the traits directly involved in the formulation of the CSR model. While imputation overestimated selection for stress tolerance, field data indicated a greater diversity of strategies, with a greater presence of competitive species. The discrepancies point to limitations in the exclusive use of imputed data in local assessments of functional diversity, highlighting the need to integrate empirical collections and improvements in imputation methods for applications in environmental management and restoration.

Foliar amino acid δ15N patterns reflect aridity and plant structure with implications for consumer diet reconstruction - Sean W. Hixon; Daniel Giddings Vassão; Ricardo Fernandes; Jörg U. Ganzhorn; Andrius Garbaras; Alison Harris; Sophia Hüsges; Balzac Mbola; Yedidya R. Ratovonamana; S. Jacques Rakotondranary; Patrick Roberts; Thomas Larsen (Phytochemistry, 2026)

Industrial settleable particulate matter promote metal(loid) bioaccumulation, metallic nanoparticle internalization and cardiac dysfunction in bullfrog tadpole - Diana Amaral Monteiro; Regiane Luiza da Costa; Iara Costa Souza; Bruno Hofstatter da Silva; Suzana Luiza Alves Fernandes; Cleoni dos Santos Carvalho; Magdalena Victoria Monferrán; Daniel Alberto Wunderlin; Marisa Narciso Fernandes (Environmental Toxicology and Pharmacology, 2026)

Mercury Bioaccumulation in Non-predatory Fish from an Indigenous Protected Area: Implications for Human Health in the Southern Amazon Basin - Yan Costa Gonçalves; Priscila Rodrigues de Siqueira; Iara da Costa Souza; Julieta Griboff; Magdalena Victoria Monferrán; Daniel Alberto Wunderlin; Manoela Maria Ferreira Marinho; Marisa Narciso Fernandes; Diana Amaral Monteiro (Exposure and Health, 2026)

Osmoregulatory disruption and metal bioaccumulation in the estuarine fish Centropomus parallelus exposed to settleable atmospheric particulate matter - Anieli Cristina Maraschi; Marco Aurelio Miranda Soares; Viviane Gomes dos Santos; Iara Costa Souza; Magdalena Victoria Monferran; Daniel Alberto Wunderlin; Fabiano Bendhack; Diana Amaral Monteiro; Marisa Narciso Fernandes (Journal of Comparative Physiology B, 2026)
Estuarine fishes experience marked environmental variability and rely on tightly regulated osmoregulatory mechanisms to maintain internal homeostasis. Settleable atmospheric particulate matter (SePM), a complex mixture of metals and metalloids, is an emerging stressor in aquatic systems and may interfere with regulatory processes. This study investigated the effects of SePM exposure on osmoregulatory homeostasis in the estuarine fish Centropomus parallelus . Fish were exposed for 96 h to either 0 g.L⁻¹ (control) or 1 g.L⁻¹ SePM, and key physiological endpoints associated with ion and water balance were assessed, including plasma osmolality and Na⁺, Cl⁻, and K⁺ concentrations; Na⁺/K⁺-ATPase (NKA), V-type H + -ATPase (VAT), and total ATPase activities in the gills and kidneys; and ionocyte abundance and transporter protein levels in gill ionocytes and renal tubules. Aluminum, iron, vanadium, and chromium levels were accumulated in the gills and kidneys. SePM exposure disrupted osmoregulatory homeostasis, as evidenced by reduced plasma osmolality and decreased Cl – and K + concentrations. NKA activity was upregulated in the gills, accompanied by an increase in the density of NKA-positive ionocytes. Conversely, total ATPase and VAT activities were downregulated in the kidneys, whereas the abundance of NKA, the symporter Na + ,K + ,2Cl − (NKCC), and the cystic fibrosis transmembrane conductance regulator (CFTR), a chloride (Cl⁻) channel, remained unchanged in renal tubules. These findings suggest that SePM exposure is associated with tissue-specific modulation of osmoregulatory parameters, including increased branchial Na⁺/K⁺-ATPase activity and NKA-positive ionocyte density, and reduced renal ATPase activities, accompanied by alterations in plasma osmolality and ion concentrations. The physiological disturbances associated with SePM exposure may impair organismal performance and reduce ecological fitness in estuarine fishes inhabiting metal-impacted coastal environments.

Type-specific sensitivity versus detection breadth in HPV diagnostics: improved analytical detection of HPV16/18 by nested PCR - Yago Tomaz Vieira da Silva; Larissa Alves Honorato Ferreira; Samara Fontes de Lima Gomes; Beatriz Helena Dantas Rodrigues De Albuquerque; Maryana Thalyta Ferreira Câmara De Oliveira; Alice Dantas Leite; José Veríssimo Fernandes; Ricardo Ney Oliveira Cobucci; Daniel Carlos Ferreira Lanza (Archives of Virology, 2026)
Accurate detection of high-risk human papillomavirus (HPV) is central to cervical cancer screening. Current diagnostic strategies increasingly prioritize broad-spectrum assays to maximize genotype coverage. However, theoretical genotype breadth does not necessarily translate into effective sample-level detection when clinically dominant targets are present at low copy number. Here, we evaluated this analytical trade-off using conventional PCR as a controlled experimental framework. Type-specific nested PCR assays targeting HPV16 and HPV18 were developed and applied to 41 cervical samples. Nested PCR showed markedly higher relative analytical sensitivity than single-round amplification and produced a greater proportion of specific and interpretable detections than the broad-spectrum consensus systems tested here (MY09/11 and GP5/6). HPV16 and/or HPV18 DNA was detected by nested PCR in 22/41 samples, whereas MY09/11 and GP5/6 detected 11/41 and 2/41 samples, respectively, under the tested conditions. These findings indicate that broad genotype coverage and effective detection of positive samples are distinct analytical properties. In settings where prevalent HPV targets occur at low abundance, a highly sensitive genotype-focused assay may reveal more target-positive samples than a broader but less sensitive consensus approach. The results are not intended to replace clinically validated broad-spectrum screening assays, but they support explicit preservation of per-target analytical sensitivity in reflex testing and future multi-target HPV assay design.

Submaximal walking increases MicroRNA-126 and angiogenic markers in men and women with peripheral arterial disease - Amauri Maroto; Tiago Fernandes; Bruno R. A. Pelozin; Anthony S. Leicht; Nelson Wolosker; Luan Morais Azevêdo; Luiz Augusto Riani Costa; Paulo Rizzo Ramires; Cláudia Lúcia de Moraes Forjaz; Natan Daniel da Silva Junior (European Journal of Applied Physiology, 2026)
Purpose Vascular dysfunction is a pathophysiological mechanism in peripheral artery disease (PAD). PAD patients exhibit reduced circulating expression of microRNA-126 (c-miRNA-126) and VEGF. Submaximal walking (SW) is recommended in PAD because it increases walking capacity, partially by improving vascular regulation, which can be observed after a walking session. Nevertheless, previous studies were conducted with maximal walking and in men. As women with PAD present worse disease characteristics and greater ischemia, they may be less responsive to SW, which needs to be investigated. Thus, this study compared the acute effects of SW on vascular function, c-miRNA-126 and angiogenic markers in men and women with PAD. Methods Thirty patients (15 women) underwent, in a random order, 2 sessions: control (standing on treadmill) and SW (15 bouts of 2-min walking at moderate intensity intersected by 2-min rest). Circulating gene expression of miRNA-126, SPRED-1, PI3KR2, VEGF, and eNOS were evaluated before and after the interventions. Results Both genders presented similar maximal walking capacity. Vascular function did not change after the interventions in either gender. After SW, both groups presented a similar decrease in PI3KR2 and similar increases in c-miRNA-126, VEGF and eNOS. Conclusion In men and women with PAD, an acute SW similarly increases c-miRNA-126 expression, which inhibits PI3KR2, enabling the progression of the VEGF angiogenic signaling pathway of PI3K-AKT-eNOS. These results support that SW is equally effective in inducing molecular angiogenic changes in men and women with PAD, supporting its recommendation for both genders. Future studies should address these possible chronic effects of walking.

Metal-rich particulate matter inhibits acetylcholinesterase activity in the brain of native estuarine fish Centropomus parallelus - Mariana Vitorino de Carvalho; Guilherme Andrade Neto Schmitz Boeing; Maira Rodrigues Lima; Rafaella Monteiro Nunes; Julieta Griboff; Fabiano Bendhack; Magdalena Victoria Monferrán; Daniel Alberto Wunderlin; Marisa Narciso Fernandes; Iara da Costa Souza (Marine Pollution Bulletin, 2026)

Effects of electrical stimulation on metabolomic and lipidomic profiles of beef Longissimus thoracis muscle - Daniel Silva Antonelo; Victória Rizzato Paschoal; Saulo da Luz e Silva; Alessandra Fernandes Rosa; Daniela Alvarez Vasco; Mariane Beline; David Edwin Gerrard; Ricardo Vieira Ventura; Júlio César de Carvalho Balieiro (Meat Science, 2026)

Can large language models implement agent-based models? An ODD-based replication study - Nuno Fachada; Daniel Fernandes; Carlos M. Fernandes; João P. Matos-Carvalho (Ecological Modelling, 2026)

Too close for comfort? Mesozooplankton dynamics in Marine Protected Areas adjacent to mining tailings on the southeastern Brazilian shelf - Bianca Salvador; Laura Rodrigues da Conceição; Renato David Ghisolfi; Mônica Souza Mendes; Tayná Rosa Martins Paiva; Valéria da Silva Quaresma; Daniel Rigo; Gustavo Martins Rocha; Paulo Sergio Salomon; Gabriel Harley Costa Santos; Priscila Teixeira-Amaral; Márcio Murilo Barboza Tenório; et al. (Marine Environmental Research, 2026)

From pest to food ingredient: Quality of Ceratits capitata larvae submitted to different methods of killing and drying - Natasha Spindola Marasca; Bruna Silva de Farias; Rafael da Silva Gonçalves; Sandro Daniel Nörnberg; Morgana Bubolz Holz; Ana Paula Dutra Resem Brizio; Sibele Santos Fernandes; Vilásia Guimarães Martins (Innovative Food Science & Emerging Technologies, 2026)

Mitigate microbial contamination and fuel degradation in marine diesel B20: Evidence from multi-analytical and metagenomic approaches - Tárcio Carneiro; Gabriel Fernandes dos Santos; Ana Carolina de Lima Barizão; Lenilson Eustáquio de Souza Junior; Larissa Bernardino Moro; Júlio Álvaro dos Santos; Mateus Souza Alvarenga; Bruno Quirino Araujo; Daniel Cruz Cavalieri; Servio Túlio Alves Cassini; Jairo Pinto de Oliveira (Bioresource Technology Reports, 2026)

Biochar in Plant Growing Media: A Scientometric Analysis (2011–2024) - Gthielly Maira Fernandes; Betelhem Fetene Admas; Emanuelly Kelly Gomes de Oliveira; Kadidja Ianne do Vale Almeida; Lívia Christina Araújo Silva de Moura; Lucrécia Pacheco Batista; Luiz Augusto Galdino Melo; Maria Helena Lima da Silva; Darliane Cristina Soares de Souza; Eulene Francisco da Silva; Daniel Valadão Silva; Rafael Oliveira Batista; et al. (Journal of Soil Science and Plant Nutrition, 2026)

Economic and Social Aspects of the Decorative Dried Plant Value Chain in the Brazilian Cerrado - Ana Carolina de Oliveira Neves; Daniel Negreiros; Renato Ramos; Lívia Echternacht; Kesley Henrique da Silva; Dimitri Fazito; Suelma Ribeiro Silva; Rodolfo Dirzo; Geraldo Wilson Fernandes (Ethnobotany and Economic Botany, 2026)
The commerce of decorative dried plants from the Brazilian Cerrado Biome provides cultural transmission, and essential revenue for low-income families. We investigated this production value chain over the past decade, assessing its economic and social relevance and mapping the main actors involved, and characterizing the interviewed participants, as well as the foreign trade trends over 50 years. Data was gathered through interviews with 67 actors across six municipalities and from official trade databases (AliceWeb and ComEx Stat). Our results show an active value chain encompassing diverse actors, products, and importing countries. Despite long-term engagement in the trade (20–50 years for most participants) and its role as the primary income source for 38.5% of respondents, 57.1% of them earn below the minimum wage. Younger generations show declining interest, influenced by economic constraints, exportation decline, stricter environmental legislation, and alternative educational and professional opportunities, including due to urbanization. However, current market transformations, including the growth of online sales, present emerging opportunities for them. While exports of dried flowers and buds have diminished considerably since the 1970s, a stable market demand for other decorative dried plant parts has persisted for nearly five decades. Finally, we suggest innovations in the value chain to support the sustainable continuity of this complex socioenvironmental system.

Himatanthus drasticus (Mart.) Plumel (APOCYNACEAE): phytochemical profile, evaluation of antibacterial and drug-potentiating activity, and toxicity of stem bark extracts - Maraiza Gregorio de Oliveira; Adrielle Rodrigues Costa; Jailson Renato de Lima Silva; Carlos Alonso leite dos Santos; Ana Raquel Pereira da Silva; Daniel Sampaio Alves; José Weverton Almeida-Bezerra; Ademar Maia Filho; José Walber Gonçalves Castro; Bárbara Fernandes Melo; Francisca de Fátima Silva de Sousa; Marcos Santos; et al. (Vegetos, 2026)

Image-based phenotyping of castor bean seeds for morphological traits, seed weight prediction, and assessment of genetic diversity - Diego Andrade Santos; Diego Fernando Marmolejo Cortes; Mylena Almeida dos Santos; Myriam El Adas; Bismarck Ferreira de Morais; Denise Barreto dos Santos; Tairone da Silva de Almeida; Christian Adalberto Santos de Queiroz; Gabriel da Paixão Fernandes; Ailan Santos de Jesus; Rafaella da Silva Rodrigues; Daniel Santos Alves; et al. (Euphytica, 2026)
Digital seed phenotyping offers an efficient and objective alternative to conventional, labor-intensive methods for morphological characterization in plant breeding programs. In castor bean, rapid and reliable tools are essential to support genetic improvement. This study evaluated the potential of digital phenotyping for seed characterization and its application in breeding. Seeds from 65 accessions (2023) and 51 accessions (2024) were photographed with an RGB camera and processed in ImageJ® for extraction of morphological traits. Agreement between digital and manual measurements was assessed by correlation and Bland–Altman analysis, while machine learning models were trained to predict hundred-seed weight (HSW). Genetic diversity was explored using principal component analysis (PCA) and clustering, and variance components and heritability were estimated with mixed linear models. Digital phenotyping showed strong agreement with manual measurements (r = 0.95–0.97) and enabled accurate HSW prediction, with Ridge Regression achieving the best performance (R 2 = 0.88; RMSE = 3.83; MAE = 3.19). PCA explained 85.7% of the variance and revealed three phenotypic clusters. Traits such as seed length (H 2 = 0.88) and aspect ratio (H 2 = 0.87) exhibited high heritability, while roundness (H 2 = 0.79), perimeter (H 2 = 0.72), and area (H 2 = 0.67) were moderate. These findings demonstrate that digital phenotyping is a reliable and high-throughput method for castor bean seed characterization, supporting genotype selection and the integration of machine learning approaches into breeding programs for greater precision and efficiency.

Water quality management and socio-hydrology strategies for an urban basin - Camila de Carvalho Almeida; Cristovão Vicente Scapulatempo Fernandes; Daniel Henrique Marco Detzel; Gemma Carr; Günter Blöschl (Hydrological Sciences Journal, 2026)

Fish biomonitoring in coastal lagoons: Assessing air-to-water contamination by metallurgical industry, neurotoxicity, and nanoparticle uptake - Mariana Vitorino de Carvalho; Julieta Griboff; William Manuel Pereira Antunes Fortes; Fabricio Alberto de Souza; Silvia Tamie Matsumoto; Magdalena Victoria Monferrán; Daniel Alberto Wunderlin; Marisa Narciso Fernandes; Iara da Costa Souza (Regional Studies in Marine Science, 2026)

Basin-wide disruption of ecological strategies of woody species induced by a dam breach in Brazil - Walisson Kenedy-Siqueira; Wénita S. Justino; Yumi Oki; Dario C. Paiva; João C. G. Figueiredo; Zhiliang Yuan; Yun Chen; Daniel Negreiros; G. Wilson Fernandes (Plant Ecology, 2026)
The Samarco dam breach in Brazil drastically altered soil and water conditions along the Rio Doce, severely impacting riparian vegetation. This study assessed how these environmental changes influenced the functional traits and ecological strategies (CSR scheme) of adult and juvenile woody plants in reference (unaffected) and impacted sites affected by mine tailings deposition. We hypothesized that mining tailings would reduce functional diversity while shifting plant strategies from stress-tolerant to competitive or ruderal. To test these hypotheses, we sampled 168 species across five regions, measuring key traits (wood density, leaf area, specific leaf area, and leaf dry matter content) and calculating functional diversity indices. RLQ analysis was applied to examine the relationship between plant traits and soil properties. In impacted sites, the plant community was less stress-tolerant than in reference sites, with a consistent reduction in community weighted mean (CWM) for S-selection. Regional responses varied: some impacted areas showed an increase in competitive species, others in ruderal, and some in both. In the adult stratum, impacted sites exhibited greater functional evenness and larger CWM leaf area, while reference sites had higher CWM leaf dry matter content and functional divergence. In the sapling stratum, reference sites had greater CWM wood density and functional richness, whereas impacted sites showed higher CWM for competitive and ruderal strategies. RLQ analysis indicated that stress-tolerant species were linked to nutrient-poor soils, while competitive species were favored in tailings-enriched environments. These findings highlight the strong filtering effect of mining tailings, which consistently reduced stress-tolerant strategies across regions and strata, leading to significant declines in functional diversity.

Arboreal Camera Trap-based Insights into the Activity, Resource Use, and Demography of Black Lion Tamarins (Leontopithecus chrysopygus) and Sympatric Mammals in Atlantic Forest Fragments - Daniel Angelo Felippi; Maria Carolina Rodella Manzano; Paolla Nicole Franco; Vinícius José Alves Pereira; João Vitor Medeiros Teixeira; João Pedro Fernandes Machado; Gabriela Cabral Rezende (International Journal of Primatology, 2026)
Wildlife monitoring is essential for guiding biodiversity conservation strategies, particularly in fragmented ecosystems under intense anthropogenic pressure. While noninvasive methods, such as camera traps, are widely used for terrestrial species, their application in other forest strata is underexplored despite its potential for studying elusive and nocturnal arboreal mammals. We aim to evaluate whether arboreal camera trapping is a relevant tool for monitoring the endangered black lion tamarin ( Leontopithecus chrysopygus ) and other sympatric arboreal and scansorial mammals in two Atlantic Forest remnants in Pontal do Paranapanema, São Paulo, Brazil. With 27 cameras in the lower and mid-canopy (0.5–8.0 m) and 9,872 camera-days, we recorded 1,316 independent video events representing seven species of mammal. Arboreal camera traps provided robust estimates of diel activity patterns, resource partitioning, and demographic dynamics, including the development of one tamarin infant and one juvenile over time. They also revealed interspecific sharing of sleeping sites and nest boxes, emphasizing the role of these structures in supporting both diurnal and nocturnal species. By documenting community-wide temporal niche partitioning, our study demonstrates how arboreal and scansorial mammals segregate activity in time when sharing the same arboreal structures. Overall, our results show that arboreal camera traps are relevant, noninvasive tool that simultaneously capture species-specific behavior, community-level interactions, and demographic information, highlighting their value for primatology, biodiversity monitoring, and integrative conservation planning in human-modified tropical forests.

Invasive Fishes Interact With Temperature to Reshape Community Size Structure Across Climatic Zones - Barbbara Silva Rocha; Ignasi Arranz; Henrique C. Giacomini; Daniel M. Perkins; Gilberto Nepomuceno Salvador; José Luís Costa Novaes; Jorge Iván Sánchez‐Botero; Angelo Antonio Agostinho; Paulo Santos Pompeu; Rosemberg Fernandes Menezes; Silvia Yasmin Lustosa‐Costa; Telton Pedro A. Ramos; et al. (Global Change Biology, 2026)
The body size spectrum (or individual size distribution) is a simple yet widely recognized approach that links individual and population traits to community structure and ecosystem functions, making it a valuable indicator of anthropogenic effects. However, the assessment of size spectra in the context of biological invasions remains poorly explored. We investigated the impacts of non‐native (NN) fish invasions on the size structure of 667 lacustrine fish communities across climatic regions (temperate, tropical, and subtropical systems) and the roles of trophic position and temperature in modulating these effects. We found that fish communities under higher invasion pressure exhibit flatter, or less negative, size spectrum exponents. Also, NN species from lower trophic levels can have greater impacts than piscivorous NNs by reshaping size spectra and reducing the overall biomass of native communities. We also observed that piscivore NNs and NNs from lower trophic levels interacted positively with temperature to drive the size spectrum exponent and total biomass of the native communities, respectively. These results can be explained by two main mechanisms: (i) NN piscivores primarily act through size‐selective predation (top–down control), which may be intensified particularly on small prey in warmer lakes, and (ii) NN fish from lower trophic levels primarily act through competition, hence reducing the numerical abundance of small‐sized native fish, which may be more vulnerable in colder and less productive lakes. These mechanisms are leading to flatter size spectrum exponents mainly at higher temperatures and to a decline in the total biomass of the native community, mainly at lower temperatures, effectively reversing the expected temperature–size rule pattern. By disentangling the trophic and temperature‐dependent mechanisms through which NN fishes affect size structure, this study strengthens our ability to anticipate the impact of biological invasions on freshwater communities and their ecosystem functions and services under global change.

Life Cycle Assessment of Biochar: A Bibliometric Analysis of Trends and Future Perspectives - Betelhem Fetene Admas; Lívia Christina de Araújo Silva Moura; Temesgen Gashaw Tarkegn; Daniel Valadão Silva; Rafael Leandro Fernandes Melo; Frederico Ribeiro do Carmo (BioEnergy Research, 2026)

Multilevel toxicological impacts of industrial settleable particulate matter in a freshwater crustacean, Macrobrachium rosenbergii - Michelly Pereira Soares; Carolina Fernandes De Angelis; Ludmila Mendes Silva; Beatriz Helena Montanari; Iara da Costa Souza; Magdalena V. Monferrán; Daniel A. Wunderlin; Marisa Narciso Fernandes; Cléo Alcantara Costa Leite (Aquatic Toxicology, 2026)

Ecological networks reveal strong pest suppression complementarity between birds and bats within rice-dominated agroecosystems in West Africa - Patrícia P. Chaves; Vanessa A. Mata; Paula Lopes; Mutaro Camará; Daniel Coimbra; Djunco Dabo; Ricardo F. de Lima; Miguel Lecoq; Gonçalo Fernandes; Patrícia Guedes; Inês Lacerda; Mark Massaad; et al. (Agriculture, Ecosystems & Environment, 2026)

Plastic pollution in the Amazon: The first comprehensive and structured scoping review - Jéssica Fernandes de Melo; Daniel Tregidgo; Anamelia Jesus; Jesem Douglas Yamall Orellana (Ambio, 2026)
Plastic pollution is a global One Health crisis, yet research has focused largely on marine environments. The Amazon—the world’s largest drainage basin and second most plastic-polluted river—has received limited scientific attention. This scoping review is the first to apply a systematic protocol (PRISMA-ScR) to assess plastic contamination across Amazonian ecosystems. We reviewed 52 peer-reviewed studies reporting plastic litter and fragments in terrestrial and aquatic environments of the biome. Most evidence concerns microplastics in Brazilian sites along the main Amazon River, with a focus on fish. However, plastics were also found in sediments, plants, and diverse fauna including birds, reptiles, and mammals. No studies reported nanoplastics. The contamination of key food and water sources poses a major One Health risk for traditional populations. We identify urgent research gaps—especially in non-fish fauna, tributaries, and other Amazonian countries—and highlight the need for targeted mitigation through waste management and education.

Antioxidant, oxidative damage and histopathological biomarkers in the gills to assess the impacts of metal/metalloid on Oreochromis niloticus inhabiting lagoons in metallurgical industrial areas - Maira Rodrigues Lima; Iara da Costa Souza; Anieli Cristina Maraschi; Caroline Martins de Souza; Julieta Griboff; Magdalena Victoria Monferrán; Daniel Alberto Wunderlin; Silvia Tamie Matsumoto; Marisa Narciso Fernandes (Science of The Total Environment, 2026)

Temporal metabarcoding of a lignocellulolytic bacterial consortium unveils compositional, structural, and potential functional adaptations - Lucas Amoroso Lopes de Carvalho; Anna Carolina de Oliveira Souza; Camila Cesário Fernandes; Eliana Gertrudes de Macedo Lemos; Lúcia Maria Carareto Alves; Daniel Guariz Pinheiro (International Biodeterioration & Biodegradation, 2026)

Unveiling the hidden consequences of mining tailings on ecosystem processes: Disruption of decomposition of native species in the Rio Doce watershed - João Carlos Figueiredo; Yule Roberta Ferreira Nunes; Walisson Kenedy-Siqueira; Renata Maia; Yumi Oki; Milton Barbosa; Débora Lima-Santos; Flávio Mariano Machado Mota; Daniel Negreiros; Letícia Ramos; Marcos Paulo dos Santos; Rebeca Ferreira Reis; et al. (Forest Ecology and Management, 2026)

Therapeutic Effects of Spent Ground Coffee Oil on Nociception, Anxiety- and Depression-Like Behaviors, and Inflammatory Mechanisms in a CFA-Induced Intraplantar Inflammation Model in Mice - Elisa Mitkus Flores Lins; Anelise Leal Vieira Cubas; Bruna Hoffmann de Oliveira; Eduarda Behenck Medeiros; Khiany Mathias; Scheila Iria Kraus; Daniel Fernandes Martins; Josiel Mileno Mack; Anna Paula Piovezan; Fabricia Petronilho; Josiane Budni; Franciane Bobinski (Molecular Neurobiology, 2026)

Integrated in Vitro, in Vivo, Molecular Docking, and ADMET in Silico Assessment of β-Caryophyllene as a NorA Efflux Pump inhibitor in Resistant Staphylococcus Aureus (MRSA) - José Weverton Almeida-Bezerra; José Thyálisson da Costa Silva; Cícera Datiane de Morais Oliveira-Tintino; Adrielle Rodrigues Costa; Viviane Bezerra da Silva; Maria Flaviana Bezerra Morais-Braga; Irwin Rose Alencar de Menezes; Ana Carolina Ferreira Araujo; Lucas Yure Santos da Silva; Daniel Sampaio Alves; Guilherme Fernandes Teixeira; Lucas dos Santos Sa; et al. (Current Microbiology, 2026)

Accuracy and accessibility in soil color determination: A comparative analysis of Munsell Chart, colorimeter, and smartphone in Amazonian soils - José Odair da Silva; João Fernandes da Silva Júnior; Lívia da Silva Santos; Gener Tadeu Pereira; Eduarda Cavalcante Amorim; Rômulo José Alencar Sobrinho; Daniel Pereira Pinheiro (Computers and Electronics in Agriculture, 2025)

Air–Water Cross-Contamination by Metalliferous Atmospheric Particulates: Bioaccumulation and Hematological Impairments in the Estuarine Fish Centropomus parallelus - Anieli Cristina Maraschi; Isabelle Cesar Moro; Viviane Gomes dos Santos; Iara Costa Souza; Magdalena Victoria Monferran; Daniel Alberto Wunderlin; Fabiano Bendhack; Marisa Narciso Fernandes; Diana Amaral Monteiro (Bulletin of Environmental Contamination and Toxicology, 2025)

Development of ingestive and social behavior of buffalo calves in a cow-calf contact grazing system - Arthur Fernandes Bettencourt; Francisco Freire Duarte; Isabelle Damé Veber Angelo; Daniel Mota-Rojas; Adriana Domínguez-Oliva; Vivian Fischer (Applied Animal Behaviour Science, 2025)

Coastal fallout of settleable particulate matter: Metal bioaccumulation and sublethal toxicity in estuarine bivalves with implications for human health - Luís Felipe de Almeida Duarte; Andressa dos Santos Barbosa Ortega; Marina de Souza Paço; Caio Rodrigues Nobre; Helen Sadauskas-Henrique; Paloma Kachel Gusso-Choueri; Iara Costa Souza; Mariana V. Carvalho; Magdalena Victoria Monferrán; Daniel Alberto Wunderlin; Marisa Narciso Fernandes; Camilo Dias Seabra Pereira (Marine Pollution Bulletin, 2025)

Bisphenol AF (BPAF) jeopardizes male fertility and triggers intergenerational defects in zebrafish (Danio rerio) - Daniel Fernandes da Costa; Luciana Marino Borali; Maya Zanardini; Eduardo Antonio Sanches; Ana Regina Seabra de Souza; Maira da Silva Rodrigues; Adriana Carvalho Natal de Moraes; Hamid R. Habibi; Rafael Henrique Nóbrega (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Transgene-free genome editing in citrus and poplar trees using positive and negative selection markers - Dhiôvanna Corrêia Rocha; Miracle Osazee Omoregbee; Danyel Fernandes Contiliani; Rushil Mandlik; Gen Li; Juliet Mascoveto; Gary Coleman; James N. Culver; Daniel Rodriguez Leal; Alessandra Alves de Souza; Yiping Qi (Plant Cell Reports, 2025)
Key message Transgene-free genome editing of the gene of interest in citrus and poplar has been achieved by co-editing the ALS gene via transient transgene expression of an efficient cytosine base editor. Abstract CRISPR-Cas genome editing systems have been widely used in plants. However, such genome-edited plants are nearly always transgenic in the first generation when Agrobacterium -mediated transformation is used. Transgene-free genome-edited plants are valuable for genetic analysis and breeding as well as simplifying regulatory approval. It can be challenging to generate transgene-free genome-edited plants in vegetatively propagated or perennial plants. To advance transgene-free genome editing in citrus and poplar, we investigated a co-editing strategy using an efficient cytosine base editor (CBE) to edit the ALS gene to confer herbicide resistance combined with transient transgene expression and potential mobile RNA-based movement of CBE transcripts to neighboring, non-transgenic cells. An FCY-UPP based cytotoxin system was used to select non-transgenic plants that survive after culturing on 5-FC containing medium. While the editing efficiency is higher in poplar than in citrus, our results show that the CBE-based co-editing strategy works in both citrus and poplar, albeit with low efficiency for biallelic edits. Unexpectedly, the addition of the TLS mobile RNA sequence reduced genome editing efficiency in both transgenic and non-transgenic plants. Although a small fraction of escaping plants is detected in both positive and negative selection processes, our data demonstrate a promising approach for generating transgene-free base-edited plants.

Examination of post-hatching starvation on oxidative stress response and larval life span in the marine ornamental shrimp, Lysmata seticaudata - Rafael C. Duarte; Daniel Acebes; Diana Madeira; Ruben X.G. Silva; Joana F. Fernandes; Fernando Ricardo; Ricardo Calado (Aquaculture, 2025)

Potential immunoprophylactic use of a multi-epitope protein of CD4+ and CD8+ T cells against visceral leishmaniasis in Balb/c mice - Scarleth Silva Costa; Naianda Rezende Ribeiro; Luiza dos Reis Cruz; Gabriel José Lucas Moreira; Vivian Tamietti Martins; Daniela Pagliara Lage; Danniele Luciana Vale; Camilly Vitória Silva Costa; Nathalia Coral Galvani; Gabriel Paulino Luiz; Maria Eduarda de Oliveira; Ricardo Andrez Machado-de-Ávila; et al. (Research in Veterinary Science, 2025)

Impacts of climate change on coastal erosion and marine flooding in Rio de Janeiro city, Brazil - João Wagner Alencar Castro; Willian Cruz Gouvea Junior; Daniel Fernandes; Caique Lima Cabral; Guilherme Tenorio Smith da Costa; Frederico Maciel Pinheiro Sampaio de Miranda; Julia Sales Serrano; Karem Moreno Carvalho; Sergio Bezerra Lima Junior (Journal of South American Earth Sciences, 2025)

Selection of microbial isolates for oxyfluorfen degradation in soil - Lais Tereza Rego Torquato Reginaldo; Matheus de Freitas Souza; Cydianne Cavalcante da Silva; Jarlan Lucas dos Santos Silva; Gilsivan Sales Medeiros de Aquino; Paulo Sergio Fernandes das Chagas; Nathan Rezende Blat; Márcia Michelle de Queiroz Ambrósio; Ioná Santos Araújo Holanda; Daniel Valadão Silva (Journal of Hazardous Materials, 2025)

Time-course detoxification of environmental metallic nanoparticles in human lung cells (A549) - Iara da C. Souza; Mariana Morozesk; Caroline M. Souza; Leticia S. Andrade; Vitor A.S. Mendes; Vinicius C. Azevedo; Rafaella Monteiro; Silvia T. Matsumoto; Magdalena V. Monferrán; Daniel A. Wunderlin; Michael Elliott; Marisa N. Fernandes (Chemosphere, 2025)

A novel zooplankton-based environmental monitoring tool for coastal impacted areas: The case of the Doce River dam rupture - Gustavo Martins Rocha; Bianca Salvador; Gabriel Harley Costa Santos; Laura Rodrigues da Conceição; Priscila Teixeira-Amaral; Maikon Di Domenico; Diego de Arruda Xavier; Eduardo Schettini Costa; Renata Caiado Cagnin; Cesar Alexandro da Silva; Mayara Bandeira; Mônica de Souza Mendes; et al. (Estuarine, Coastal and Shelf Science, 2025)

Effects of bisphenol A alternatives (BPS and BPAF) on zebrafish (Danio rerio) spermatogenesis ex vivo: meiosis damage and transcriptional deregulation of genes related to spermatogenic processes and epigenetic regulation - Daniel Fernandes da Costa; Maira da Silva Rodrigues; Luciana Marino Borali; Beatriz Marques de Souza; Hamid R. Habibi; Rafael Henrique Nóbrega (Environmental Toxicology and Pharmacology, 2025)

Corrigendum to “Application of sensing techniques for quantifying CO2 flux and dynamics in environments affected by the Fundão dam collapse, Mariana, Brazil” [J. S. Am. Earth Sci. 146 (2024) 105099 – pages 1–9] - Heitor Paiva Palma; Danilo César de Mello; Márcio Rocha Francelino; Daniela Schmitz; Gustavo Vieira Veloso; Ana Paula Marinho Santos; Daniel Nunes Krum; André Thomazini; Elpídio Inácio Fernandes-Filho; Carlos Ernesto Gonçalves Reynaud Schaefer; José A.M. Demattê (Journal of South American Earth Sciences, 2025)

Metatranscriptomic profiling reveals microbial succession and adaptation strategies during long-term lignocellulose degradation - Lucas Amoroso Lopes de Carvalho; Anna Carolina de Oliveira Souza; Camila Cesário Fernandes; Cleiton Dias do Prado; Eliana Gertrudes de Macedo Lemos; Lúcia Maria Carareto Alves; Daniel Guariz Pinheiro (International Biodeterioration & Biodegradation, 2025)

Bioaccessibility and availability of trace elements coprecipitated with aluminum-substituted iron oxides - Daniel Kroehling; Renato Welmer Veloso; Jaime Wilson Vargas de Mello; André Mundstock Xavier de Carvalho; Marcelo Fernandes de Oliveira; Isabela Cristina Filardi Vasques (Environmental Geochemistry and Health, 2025)

Chemical and physical characterization of atmospheric particulate matter under metallurgical influence and its biochemical effects on Allium cepa L. cells - Iasmini Nicoli Galter; Iara da Costa Souza; Enzo Zini Moreira Silva; Adrislaine da Silva Mansano; Magdalena V. Monferrán; Daniel A. Wunderlin; Francielen Barroso Aragão; Marisa Narciso Fernandes; Silvia Tamie Matsumoto (Ecotoxicology, 2025)

Ingestive behavior of dairy buffaloes in a cow-calf contact grazing system during the post-calving - Arthur Fernandes Bettencourt; Francisco Freire Duarte; Isabelle Damé Veber Angelo; Júlia Fernandes Aires; Bruna Martins de Menezes; Anderson Michel Soares Bolzan; Daniel Mota-Rojas; Vivian Fischer (Applied Animal Behaviour Science, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Harnessing arabica and canephora coffee cascara as substrates for kombucha: Comparative study of chemical, antioxidant, antibacterial and antifungal properties - Mariana Moysés Delorme; Beatriz Spena Machado; Fernanda dos Santos Ferreira; Rayssa Neves Alves; Daniel Coelho Ferreira; Jessica Pronestino de Lima Moreira; Vanessa Naciuk Castelo-Branco; Thais Matsue Uekane; Fabrício Freitas Fernandes; Adriene Ribeiro Lima (Biocatalysis and Agricultural Biotechnology, 2025)

Seed Priming with Brassinosteroids Mitigates Pre-Flowering Drought Stress in Soybean Varieties - Sebastião de Oliveira Maia Júnior; Jailma Ribeiro de Andrade; Valéria Fernandes de Oliveira Sousa; Patrick Costa Silva; Danielle Lopes Aguiar; Antônio Moisés de Sousa Torres; Daniel Cutrim Diniz; Fábio Afonso Mazzei Moura de Assis Figueiredo; Fabrício de Oliveira Reis; Tiago Massi Ferraz (Journal of Soil Science and Plant Nutrition, 2025)

Muscle oxidative stress, neurotoxicity and human health risks from consuming fish exposed to metallic settleable atmospheric particulate matter - Mariana V. Carvalho; Rafaella Monteiro; Iara da C. Souza; Julieta Griboff; Fabiano Bendhack; Magdalena V. Monferrán; Daniel A. Wunderlin; Marisa N. Fernandes (Marine Pollution Bulletin, 2025)

Modeling the adsorption of ciprofloxacin on magnetic biochar: A comparative study of traditional and advanced approaches - Ana Carolina Ferreira Piazzi Fuhr; Daniel Lucas Costa Rodrigues; Júlia Amaral Guido; Cristiane Ferraz de Azevedo; Nicholas Fernandes de Souza; Guilherme Luiz Dotto; Eder Claudio Lima; Fernando Machado Machado (Journal of Water Process Engineering, 2025)

Gluten-free cookies: A comprehensive review of substitutes for wheat flour - Rafael Fernandes Almeida; Lara Aguiar Borges; Daniel Anacleto; Miriam Stephanie Nunes de Souza; Licymara Brianne Magalhães da Silva; Yaneth Machaca Monroy; Eduardo Augusto Caldas Batista; Ana Paula Oliveira Machado (Food and Humanity, 2025)

Non-native fishes occupy broader isotopic niche than native fishes in an impaired river system - Daniel Azarias Rezende da Silva; Débora Reis de Carvalho; Frederico Fernandes Ferreira; Jorge A. Dergam; Marcelo Zacharias Moreira; Paulo Santos Pompeu (Hydrobiologia, 2025)

Analysis of environmental fragility in a mineral exploration area in the Southern Region of Brazil - Pedro Daniel da Cunha Kemerich; Leonardo Rosa da Silva; Douglas Stefanello Facco; Milene Priebe e Silva; Gabriel DAvila Fernandes; Willian Fernando de Borba; Fernando Ernesto Ucker; Luciano Marquetto (Arabian Journal of Geosciences, 2025)

The role of mitochondrial dysfunction and calcium dysregulation in 2C-I and 25I-NBOMe-induced neurotoxicity - Eva Gil-Martins; Fernando Cagide; Ana Borer; Daniel José Barbosa; Carlos Fernandes; Daniel Chavarria; Fernando Remião; Fernanda Borges; Renata Silva (Chemico-Biological Interactions, 2025)

Aerosol optical depth over Northeastern Brazil: A multi-platform intercomparison study - Gabriel Bonow Münchow; Aline Macedo de Oliveira; Ediclê De Souza Fernandes Duarte; Daniel Camilo Fortunato dos Santos Oliveira; Bárbara Marinho Araujo; Nilton Manuel Évora do Rosário; Judith Johanna Hoelzemann (Atmospheric Research, 2025)

Single-step sustainable production of activated carbon from microalgal biomass: An approach to waste recovery from urban wastewater - Renata Estevam; Ricardo Franci Gonçalves; Daniel Fernandes Cipriano; Janaína Simões Lima; Miguel Ângelo Schettino Junior (Algal Research, 2025)

Ontogenetic trajectories and sexual dimorphism of a neotropical ground snake genus Erythrolamprus (Serpentes: Dipsadidae) - Daniel Silva Fernandes; Cristiane Barros Régis (Zoology, 2025)

Effects of the insecticide thiodicarb on non-target organs and behavior of the stingless bee Partamona helleri (Hymenoptera: Meliponini) - Davy Soares Gomes; Franciane Rosa Miranda; João Victor de Oliveira Motta; Mateus Soares de Oliveira; Cliver Fernandes Farder-Gomes; Daniel Silva Sena Bastos; Rodrigo Cupertino Bernardes; Fernanda Pereira da Silva; Pollyana Leão Gonçalves; Hugo Bolsoni Zago; Cynthia Canêdo da Silva; Leandro Licursi de Oliveira; et al. (Pesticide Biochemistry and Physiology, 2025)

Artificial neural networks to estimate the sorption and desorption of the herbicide linuron in Brazilian soils - Lucrecia Pacheco Batista; Luma Lorena Loureiro da Silva Rodrigues; Matheus de Freitas Souza; Paulo Sérgio Fernandes das Chagas; Stefeson Bezerra de Melo; Ana Beatriz Rocha de Jesus Passos; María Carolina Ramírez Hernández; Mayara Alana Silvestre Araújo; Daniel Valadão Silva (Environmental Pollution, 2025)

Assessing the Contaminat Plume of a Coastal Cemitery in Sandy Soils - Gabriel D’ávila Fernandes; Willian Fernando de Borba; Pedro Daniel da Cunha Kemerich; Éricklis Edson Boito de Souza; Filipi Godinho Veiga; Lenon Mello Ilha; Daniel Gustavo Allasia Piccilli (Water, Air, & Soil Pollution, 2025)

Mining tailings severely impact plant communities in a rainforest watershed - G. Wilson Fernandes; Letícia Ramos; Wénita de Souza Justino; Walisson Kenedy-Siqueira; João Carlos Gomes Figueiredo; Yumi Oki; Fernando Figueiredo Goulart; Rubens Manoel dos Santos; João Herbert Moreira Viana; Yule Roberta Ferreira Nunes; Ramiro Aguilar; Lourens Poorter; et al. (Anthropocene, 2025)

Understanding the effects of Bothrops erythromelas and Bothrops leucurus venoms on human blood coagulation - Eduardo Oliveira Venancio de Lima; Lídia Jorge Tasima; Daniela Miki Hatakeyama; Maria Amélia Farias Rodrigues; Caroline Serino-Silva; Daniel Rodrigues Stuginski; Giovanni Perez Machado da Silveira; Benedito Carlos Prezoto; Kathleen Fernandes Grego; Sávio Stefanini Sant’Anna; Anita Mitico Tanaka-Azevedo; Karen de Morais-Zani (Toxicon, 2025)

Pulses of life: Wet events in Botucatu Paleodesert evidenced by trace fossils analysis (earliest Cretaceous, Paraná Basin, Brazil) - Bernardo Peixoto; Daniel Sedorko; Gabriel E.B. de Barros; Heitor Francischini; Renato P. Ghilardi; Marcelo A. Fernandes (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Use of marine anthropogenic litter as a potential risk of pollution to the burrowing owl (Athene cunicularia) on the beaches of the Brazilian Amazon coast - Dayene Santiago Mendes; Daniel Nobre Nunes Silva; Davidson Sodré; Ubiratan Pinheiro Júnior; Paula Danielle Lima da Silva; Denis Domingues; José Luiz Vieira Costa Neto; Leônidas Dahás Jorge de Souza; Marcus Emanuel Barroncas Fernandes (Environmental Pollution, 2025)

Towards the reference ecosystems for quartzitic campo rupestre: Floristic composition and soil relationships - Jéssica Cunha-Blum; Letícia Ramos; Daniel Negreiros; Dario C. Paiva; Vanessa M. Gomes; Leonardo M. Borges; Aristônio M. Teles; G. Wilson Fernandes (Ecological Engineering, 2025)

Genetic and biochemical determinants in potentially toxic metals resistance and plant growth promotion in Rhizobium sp LBMP-C04 - Daiane Silva Bonaldi; Michelli Inácio Gonçalves Funnicelli; Camila Cesário Fernandes; Henrique Fontellas Laurito; Daniel Guariz Pinheiro; Lucia Maria Carareto Alves (World Journal of Microbiology and Biotechnology, 2025)

Methyl Jasmonate Mitigates Drought Stress in Purple Basil by Enhancing Photosynthesis and Secondary Metabolism - Adriano Salviano Lopes; Thiago Jardelino Dias; Juliane Maciel Henschel; João Henrique Barbosa da Silva; Valéria Fernandes de Oliveira Sousa; Vitor Araújo Targino; Marcia Paloma da Silva Leal; Daniel da Silva Gomes; Manoel Bandeira de Albuquerque; Diego Silva Batista (Journal of Plant Growth Regulation, 2025)

When a name changes everything: taxonomy and conservation of the Atlantic bushmaster ( Lachesis Daudin, 1803) (Serpentes: Viperidae: Crotalinae) - Breno Hamdan; Sandro L. Bonatto; Dennis Rödder; Victor Corrêa Seixas; Rogério Mercês Ferreira Santos; Diego José Santana; Larissa Gonçalves Machado; Jessica Matos Kleiz-Ferreira; Marco A. de Freitas; Rodrigo Castellari Gonzalez; Thabata Cavalcante; Moisés Barbosa de Souza; et al. (Systematics and Biodiversity, 2024)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Dynamics of metal/metalloid bioaccumulation and sensitivity in post-larvae shrimp (Macrobrachium rosenbergii) exposed to settleable atmospheric particulate matter from an industrial source - Michelly Pereira Soares; Carolina Fernandes De Angelis; Edwin W. Taylor; Ludmila Mendes Silva; Beatriz Helena Montanari; Vinicius Cavicchioli Azevedo; Iara da Costa Souza; Magdalena V. Monferrán; Daniel A. Wunderlin; Marisa Narciso Fernandes; Cléo Alcantara Costa Leite (Science of The Total Environment, 2024)

Effects of metallic dust on Nile tilapia: Exploring the relationship between metal bioaccumulation, metallothionein levels, and oxidative stress responses - Anieli Cristina Maraschi; Henrique Aio Adorno; Yan Costa Gonçalves; Iara Costa Souza; Magdalena Victoria Monferrán; Daniel Alberto Wunderlin; Marisa Narciso Fernandes; Diana Amaral Monteiro (Science of The Total Environment, 2024)

Dam removal effects on carbon processing in a mountainous Mediterranean stream - João Miguel Merces Bega; Davi Gasparini Fernandes Cunha; Margarita Menéndez López; Alba Camacho-Santamans; Daniel von Schiller (Science of The Total Environment, 2024)

Polysaccharide fractions extracted from Lactarius quieticolor mushroom exhibit immune stimulatory activities on macrophages - Matheus Zavadinack; Daniel de Lima Bellan; Maria Paula Fernandes Bonaldi; Shayane da Silva Milhorini; Lucimara M.C. Cordeiro; Fernanda Fogagnoli Simas; Marcello Iacomini (Food Research International, 2024)

Effects of a Ketogenic Diet on the Assessment of Biochemical and Clinical Parameters in Duchenne Muscular Dystrophy: A Preclinical Investigation - Lilian Leite Fausto; Adriano Alberti; Gabriela Kades; Risoní Pereira Dias de Carvalho; Viviane Freiberger; Leticia Ventura; Paula Dias; Eliton Marcio Zanoni; Ben Hur Soares; Matheus Luchini Dutra; Daniel Fernandes Martins; Clarissa Martinelli Comim (Molecular Neurobiology, 2024)

First report of Meloidogyne javanica infecting Thymus vulgaris in the state of São Paulo, Brazil - Edicleide Macedo da Silva; Ricardo Koroiva; Rivanildo Júnior Ferreira; Daniel Dalvan do Nascimento; João Pedro Peixoto Fernandes; Benedito Charlles Damasceno Neves; Antonio Cesar de Araujo Filho; Rafaelle Fazzi Gomes; Nynyve Thaynar Brito de Almeida; Andréia Mitsa Paiva Negreiros; Pablo Forlan Vargas; Laura Raissa Fagundes Costa Bezerra; et al. (Crop Protection, 2024)

Soil and vegetation types are predisposition factors controlling greenness changes: A shift of paradigm in greening and browning modelling? - Luís Flávio Pereira; Elpídio Inácio Fernandes-Filho; Lucas Carvalho Gomes; Daniel Meira Arruda; Guilherme Castro Oliveira; Carlos Ernesto Gonçalves Reynald Schaefer; José João Lelis Leal de Souza; Márcio Rocha Francelino (Remote Sensing Applications: Society and Environment, 2024)

Mining Tailings Effects on Soil Quality and Performance of Two Native Species of Atlantic Forest: Implications for Restoration - Bárbara Dias Araújo; Renata A. Maia; Milton Barbosa; Thamara F. Silva; Luzia Valentina Modolo; Daniel Negreiros; Geraldo Wilson Fernandes (Water, Air, & Soil Pollution, 2024)

Construction and demolition waste as a low-cost adsorbent for water treatment: kinetics, isotherm, thermodynamics, and Fenton regeneration - Danilo H. S. Santos; Larissa F. Queiroz; Luiz D. Silva Neto; Keven E. Santos; Denio D. C. S. das Neves; Anamália F. Silva; Eduardo J. S. Fonseca; Daniel P. Fernandes; Lucas Meili (Environmental Science and Pollution Research, 2024)

The role of carapace colour in species recognition in a fiddler crab - Diogo Jackson Aquino Silva; Marilia Fernandes Erickson; Daniel Marques Almeida Pessoa (Animal Behaviour, 2024)

Application of sensing techniques for quantifying CO2 flux and dynamics in environments affected by the fundão dam collapse, mariana, Brazil - Heitor Paiva Palma; Danilo César de Mello; Márcio Rocha Francelino; Daniela Schmitz; Gustavo Vieira Veloso; Ana Paula Marinho Santos; Daniel Nunes Krum; André Thomazini; Elpídio Inácio Fernandes-Filho; Carlos Ernesto Gonçalves Reynaud Schaefer; Teogenes Senna de Oliveira; José A.M. Demattê (Journal of South American Earth Sciences, 2024)

The impact of settleable atmospheric particulate on the energy metabolism, biochemical processes, and behavior of a sentinel mangrove crab - Anieli C. Maraschi; Cesar Rubio-Lopez; Solana M. Snitman; Iara C. Souza; Brian Pichardo-Casales; Guillermina Alcaraz; Magdalena V. Monferrán; Daniel A. Wunderlin; Claudia Caamal-Monsreal; Carlos Rosas; Marisa N. Fernandes; Mariana V. Capparelli (Journal of Hazardous Materials, 2024)

Foreshadowing an exponential market: A brief story, applications, and perspectives of CRISPR/Cas system for the production of (hemi-)cellulases in filamentous fungi - Felipe Ferreira Silva; Natana Gontijo Rabelo; Klédna Constância Reis; Cássio Siqueira Souza Cassiano; Anderson Fernandes de Melo; Débora de Oliveira Lopes; Wagner Rodrigo de Souza; Marina Quádrio R.B. Rodrigues; Daniel Bonoto Gonçalves (Fungal Biology Reviews, 2024)

Exposure to the herbicide tebuthiuron affects behavior, enzymatic activity, morphology and physiology of the midgut of the stingless bee Partamona helleri - Cliver Fernandes Farder-Gomes; Franciane Rosa Miranda; Rodrigo Cupertino Bernardes; Daniel Silva Sena Bastos; Davy Soares Gomes; Fernanda Pereira da Silva; Pollyana Leão Gonçalves; Stella Arndt; André da Silva Xavier; Hugo Bolsoni Zago; José Eduardo Serrão; Gustavo Ferreira Martins; et al. (Environmental Toxicology and Pharmacology, 2024)

Exploring the biofilm inhibitory potential of Candida sp. UFSJ7A glycolipid on siliconized latex catheters - Cibele Garcia Bastos; Diego Fernandes Livio; Maria Auxiliadora de Oliveira; Hiure Gomes Ramos Meira; Vinícius Souza Tarabal; Heloísa Carneiro Colares; Adriano Guimarães Parreira; Rafael César Russo Chagas; Marcelo Gomes Speziali; José Antônio da Silva; José Mauro Granjeiro; Ruben Dario Sinisterra Millán; et al. (Brazilian Journal of Microbiology, 2024)

Acquisition of elemental sulfur by sulfur‐oxidising Sulfolobales - Maria C. Fernandes‐Martins; Carli Springer; Daniel R. Colman; Eric S. Boyd (Environmental Microbiology, 2024)
Elemental sulfur (S 8 0 )‐oxidising Sulfolobales (Archaea) dominate high‐temperature acidic hot springs (>80°C, pH 8 0 ‐oxidising members of the Sulfolobales reveal a patchy distribution of genes encoding sulfur oxygenase reductase (SOR), an S 8 0 disproportionating enzyme attributed to S 8 0 oxidation. Here, we report the S 8 0 ‐dependent growth of two Sulfolobales strains previously isolated from acidic hot springs in Yellowstone National Park, one of which associated with bulk S 8 0 during growth and one that did not. The genomes of each strain encoded different sulfur metabolism enzymes, with only one encoding SOR. Dialysis membrane experiments showed that direct contact is not required for S 8 0 oxidation in the SOR‐encoding strain. This is attributed to the generation of hydrogen sulfide (H 2 S) from S 8 0 disproportionation that can diffuse out of the cell to solubilise bulk S 8 0 to form soluble polysulfides (S x 2− ) and/or S 8 0 nanoparticles that readily diffuse across dialysis membranes. The Sulfolobales strain lacking SOR required direct contact to oxidise S 8 0 , which could be overcome by the addition of H 2 S. High concentrations of S 8 0 inhibited the growth of both strains. These results implicate alternative strategies to acquire and metabolise sulfur in Sulfolobales and have implications for their distribution and ecology in their hot spring habitats.

Metaflumizone susceptibility baseline, reproduction, locomotion, and respiration responses on the Hypothenemus hampei - Caio S. Soares; Antônio G. de O. Nascimento; Natan S. Rocha; Ryan F.S. Silva; Daniel C. Nogueira; Jairo Tronto; Maria E.de S. Fernandes; Flávio L. Fernandes (Crop Protection, 2024)

Systemic effects of settleable atmospheric particulate matter (SePM) on swamp ghost crab Ucides cordatus - Caio Rodrigues Nobre; Marina de Souza Paço; Luis Felipe de Almeida Duarte; Andressa dos Santos Barbosa Ortega; Beatriz Barbosa Moreno; Thiago Felicíssimo Turíbio de Camargo; Leticia Malvestio Parreira; Iara da Costa Souza; Magdalena Victoria Monferrán; Daniel Alberto Wunderlin; Marisa Narciso Fernandes; Camilo Dias Seabra Pereira (Science of The Total Environment, 2024)

Comprehensive risk assessment of microplastics in tidal channel sediments in amazonian mangroves (northern Brazil) - Dayene Santiago Mendes; Daniel Nobre Nunes Silva; Luiz Eduardo Pereira Santiago; Vando José Costa Gomes; Colin Robert Beasley; Marcus Emanuel Barroncas Fernandes (Journal of Environmental Management, 2024)

Magnetic refrigeration enhanced by magnetically-activated thermal switch: An experimental proof-of-concept - Vivian M. Andrade; Cláudia R. Fernandes; Daniel J. Silva; Joana S. Teixeira; Clara R. Pereira; Rita Duarte; Ana L. Pires; João Ventura; Joana Oliveira (International Journal of Refrigeration, 2024)

Facilitation and allelopathy mediate phylogenetic and functional diversity under Atlantic Rainforest trees - Cristiani Spadeto; Daniel Negreiros; Cássio Cardoso Pereira; Cássio Alencar Nunes; Lorena Abdalla de Oliveira Prata Guimarães; Sustanis Horn Kunz; G. Wilson Fernandes (Flora, 2024)

Melia azedarach L. in vitro plantlets as a new source of antifeeding salannin- and nimbolinin-type limonoids - Daniel Yuri Akiyama; Maria Eduarda Radavelli Santos; Marina Ferreira Maximo; Maria de Fátima das Graças Fernande da Silva; Adriana Aparecida Lopes; Taicia Pacheco Fill (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Exploratory comparative transcriptomic analysis reveals potential gene targets associated with Cry1A.105 and Cry2Ab2 resistance in fall armyworm (Spodoptera frugiperda) - Tereza Cristina L. Castellane; Camila C. Fernandes; Daniel G. Pinheiro; Manoel Victor Franco Lemos; Alessandro M. Varani (Functional & Integrative Genomics, 2024)

Production and characterization of the lipopeptide with anti-adhesion for oral biofilm on the surface of titanium for dental implants - Fernanda Souza Carvalho; Vinícius Souza Tarabal; Diego Fernandes Livio; Luísa F. Cruz; Ana P.F. Monteiro; Adriano Guimarães Parreira; Pedro P.G. Guimarães; Karina Scheuerman; Rafael Cesar Russo Chagas; José Antônio da Silva; Daniel Bonoto Gonçalves; José Mauro Granjeiro; et al. (Archives of Microbiology, 2024)

Cork oak woodlands and decline: a social-ecological review and future transdisciplinary approaches - Margarida Lopes-Fernandes; Ernesto Martínez-Fernández; Rui Alves; Daniel Boa-Nova; Cristina Branquinho; Miguel N Bugalho; Felipe Campos-Mardones; Agustin Coca-Pérez; Amélia Frazão-Moreira; Marco Marques; Javier Moreno-Ortiz; Octávio Paulo; et al. (Agroforestry Systems, 2024)
Cork oak woodlands are socio-ecosystems recognized as biodiversity hotspots, a fundamental economic source for companies and local communities as well as an identitarian landscape for residents and visitors. Cork oak woodlands, however, are facing tree mortality and lack of regeneration. Considering the oak decline scenario, we present Iberian cork oak montado/dehesa as a socio-ecosystem facing climate change, management transformations, local knowledge crisis and social uncertainty. We review montado s/ dehesa s research through time and by different scholar perspectives. We defend that from an interdisciplinary and transdisciplinary perspective, including the experience and evidence observed in terrain, debate should be stimulated, and novel conceptual approaches may contribute to finding solutions. We argue that the confluence of ecology, genetics, anthropology and local knowledge can be explored to unveil the complexities and the challenges of these socio-ecosystems and contribute to prevent and mitigate threats to it. We propose a methodological approach built together with scientists, managers and workers, that can explore oak translocations, socio-ecological interactions models, knowledge transfer and other ways to overcome Iberian cork oak woodlands socio-environmental crisis.

Sensitivity and antioxidant response of forest species seedlings to the atrazine under simulated conditions of subsurface water contamination - Francisco Assis Nogueira Neto; Matheus de Freitas Souza; Nathan Rezende Blat; Francisca Daniele da Silva; Bruno Caio Chaves Fernandes; Paulo Sergio Fernandes das Chagas; Poliana Coqueiro Dias Araujo; Hamurábi Anizio Lins; Daniel Valadão Silva (Chemosphere, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Impact of replacing protein pellets with soybean grain on nutrient utilization and the rumen and blood parameters of feedlot cattle under tropical conditions - Daniel Henrique Souza Tavares; Julián Andrés Castillo Vargas; Vera Lúcia de Araújo Bozorg; Jose Neuman Miranda Neiva; José Helder de Andrade Moura; Ithalo Barros Freitas; Thays Matias da Silva Pinto; Luciano Fernandes Sousa; Fabrícia Rocha Chaves Miotto (Tropical Animal Health and Production, 2024)

Exposure to low-concentration fipronil impairs survival, behavior, midgut morphology and physiology of Aedes aegypti larvae - Cliver Fernandes Farder-Gomes; Franciane Rosa Miranda; Kenner Morais Fernandes; Rodrigo Cupertino Bernardes; Daniel Silva Sena Bastos; Leandro Licursi de Oliveira; Gustavo Ferreira Martins; José Eduardo Serrão (Chemosphere, 2024)

Effect of acute exposure to settleable atmospheric particulate matter emitted by the steel industry on hematology and innate immunity of fat snook (Centropomus parallelus) - Michelly Pereira Soares; Ludmila Mendes Silva; Carolina Fernandes De Angelis; Israel Luz Cardoso; Edwin W. Taylor; Iara da Costa Souza; Fabiano Bendhack; Nathan de Souza Vieira; Magdalena V. Monferrán; Daniel A. Wunderlin; Marisa Narciso Fernandes; Cléo Alcantara Costa Leite (Marine Pollution Bulletin, 2024)

Seasonality in Crotalus durissus venom - Lidia Jorge Tasima; Eduardo Oliveira Venâncio de Lima; Daniela Miki Hatakeyama; Jarbas Prado Vidueiros; Daniel Rodrigues Stuginski; Kathleen Fernandes Grego; Anita Mitico Tanaka-Azevedo (Toxicon, 2024)

Dissimilar forests along the Rio Doce watershed call for multiple restoration references to avoid biotic homogenization - Letícia Ramos; Daniel Negreiros; Fernando Figueiredo Goulart; João Carlos Gomes Figueiredo; Walisson Kenedy-Siqueira; Tiago Shizen Pacheco Toma; Wénita de Souza Justino; Renata A. Maia; Jéssica Tetzner de Oliveira; Yumi Oki; Milton Barbosa; Ramiro Aguilar; et al. (Science of The Total Environment, 2024)

Parametric resonance of subsea foundation template during installation - Emerson Martins de Andrade; Daniel de Oliveira Costa; Antonio Carlos Fernandes; Joel Sena Sales Junior (Ocean Engineering, 2024)

Assessment of groundwater quality from monitoring wells in an area occupied by a cemetery in South Brazil - Gabriel D’ávila Fernandes; Willian Fernando de Borba; Paula Dalla Vecchia; Sérgio Roberto Mortari; Fábio Andrei Duarte; Pedro Daniel da Cunha Kemerich; Éricklis Edson Boito de Souza; José Luiz Silvério da Silva; Milene Priebe e Silva; Mateus Guimarães da Silva; Joao Pedro Berton Wissmann (Arabian Journal of Geosciences, 2024)

Anticorrosive properties in 1020 steel of an alkaloid-rich extract obtained from the jaborandi biomass (Pilocarpus microphyllus staff ex wardlew) of the pilocarpine industrial production chain - Francisco Marcelino Almeida de Araújo; Emely Thainara Almeida de Araújo; Miguel Gomes Cardoso; Bruno Silva Sá; Leiz Maria Costa Veras; Andreanne Gomes Vasconcelos; David Fernandes Lima; João Gonçalves; Augusto Batagin-Neto; Luciene Costa Vasconcelos; Massimo Lucarini; Alessandra Durazzo; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)

Comments on Palanisamy et al. (2024) “Spatio-temporal analysis of shoreline changes and future forecast using remote sensing, GIS and kalman filter model: A case study of Rio de Janeiro, Brazil” - João Wagner Alencar Castro; Daniel Fernandes; Willian Cruz Gouvea Junior; Frederico Maciel Pinheiro Sampaio de Miranda; Lucas Lavo Antonio Jimo Miguel (Journal of South American Earth Sciences, 2024)

Longshore sediment transport rate in Formosa Bay, Rio de Janeiro State - Southeast Brazil - Daniel Fernandes; João Wagner Alencar Castro (Journal of South American Earth Sciences, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Oxidative stress and neurotoxicity induced by exposure to settleable atmospheric particulate matter in bullfrog tadpoles, Aquarana catesbeiana, (Shaw, 1802) - Isabela Ferreira Fernandes; Gabriel Hiroshi Fujiwara; Heidi Samantha Moraes Utsunomiya; Iara Costa Souza; Diana Amaral Monteiro; Magdalena Victoria Monferrán; Daniel Alberto Wunderlin; Marisa Narciso Fernandes; Cleoni dos Santos Carvalho (Chemosphere, 2024)

Evaluation of dual-energy X-ray absorptiometry (DXA) technique for the determination of body composition of Pacu and Nile tilapia in vivo - Cleber Fernando Menegasso Mansano; Edney Pereira da Silva; Kifayat Ullah Khan; Thiago Matias Torres do Nascimento; Nilva Kazue Sakomura; Andressa Tellechea Rodrigues; André Zuffo Boaratti; Rafael de Souza Romaneli; Daniel Monge de Almeida Queiroz; Juliana Heloisa Pinê Américo-Pinheiro; Acacio Aparecido Navarrete; Beatrice Ingrid Macente; et al. (Aquaculture, 2024)

Molecular survey of hemoplasmas and Coxiella burnetii in vampire bats from northern Brazil - Victória Valente Califre de Mello; Laryssa Borges de Oliveira; Taciana Fernandes Souza Barbosa Coelho; Daniel Antonio Braga Lee; Eliz Oliveira Franco; Rosangela Zacarias Machado; Marcos Rogério André (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Pest Monitoring Reduces Costs and Increases Revenue in the Solanum tuberosum Potato Crop - Ítalo W. da Silva; Monique F. Malaquias; Daniel C. Nogueira; Erick A. A. Rocha; Ronald M. Silva; Carlos G. da Cruz; Flávio L. Fernandes (Potato Research, 2024)

Floristic composition and edaphic relationships in ferruginous campo rupestre reference ecosystems - G. Wilson Fernandes; Letícia Ramos; Dario C. Paiva; Jéssica Cunha-Blum; Vanessa Matos Gomes; Daniel Negreiros (Journal of Mountain Science, 2024)

An integrated approach to decision-making variables on urban water systems using an urban water use (UWU) decision-support tool - Taiane Regina Hoepers; Juliana Leithold; Michel Marques Monteiro; Gerald A. Corzo Perez; Cristovão V. Scapulatempo Fernandes; Chris Zevenbergen; Daniel Costa dos Santos (Science of The Total Environment, 2024)

Developing expert scientific consensus on the environmental and societal effects of marine artificial structures prior to decommissioning - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Todd Bond; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Jennifer Dannheim; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

Enhancing Methylene Blue Dye Removal using pyrolyzed Mytella falcata Shells: Characterization, Kinetics, Isotherm, and Regeneration through Photolysis and Peroxidation - Renata Silva de Lima; Josealdo Tonholo; Selvasembian Rangabhashiyam; Daniel Pinto Fernandes; Jordana Georgin; Carmem Lúcia de Paiva e Silva Zanta; Lucas Meili (Environmental Management, 2024)

Exploring the neuroprotective potential of antimicrobial peptides from Dinoponera quadriceps venom against pentylenetetrazole-induced seizures in vivo - Livia Correia Fernandes Paes; Dânya Bandeira Lima; Daniel Moreira Alves da Silva; José Tiago Valentin; Pedro Everson Alexandre de Aquino; Alicia Belén García-Jareño; Mar Orzaéz; Marta Maria de França Fonteles; Alice Maria Costa Martins (Toxicon, 2024)

Toxic, genotoxic, mutagenic, and bioaccumulative effects of metal mixture from settleable particulate matter on American bullfrog tadpoles (Lithobates catesbeianus) - Regiane Luiza da Costa; Iara Costa Souza; Mariana Morozesk; Luana Beserra de Carvalho; Cleoni dos Santos Carvalho; Magdalena Victoria Monferrán; Daniel Alberto Wunderlin; Marisa Narciso Fernandes; Diana Amaral Monteiro (Environmental Pollution, 2024)

Patterns of occurrence of the sub-Antarctic fur seal Arctocephalus tropicalis (Gray 1872) in Southern Brazil: climatic and environmental associations - Carlos de Oliveira; Murilo Guimarães; Lucas Schroeder; Marcelo Zagonel-Oliveira; Gyrlene Aparecida Mendes da Silva; Márcio Borges-Martins; Daniel Danilewicz; Jonatas Henrique Fernandes Prado; Venisse Schossler; Silvina Botta; Eduardo Resende Secchi; Francisco Eliseu Aquino; et al. (Polar Biology, 2024)

Metal/metalloid bioconcentration dynamics in fish and the risk to human health due to water contamination with atmospheric particulate matter from a metallurgical industrial area - William Manuel Pereira Antunes Fortes; Iara da Costa Souza; Vinicius Cavicchioli Azevedo; Julieta Griboff; Magdalena Victoria Monferrán; Daniel Alberto Wunderlin; Silvia Tamie Matsumoto; Marisa Narciso Fernandes (Science of The Total Environment, 2023)

Integration of seismic stratigraphy and cyclostratigraphy for high resolution chronostratigraphic correlation: The Albacora Field, Campos Basin, Brazil - Braun Natália Santos; Ciro Climaco Rodrigues; Daniel Ribeiro Franco; Mingsong Li; Mariana Aragão Fernandes; Mariane Candido; Raysa de Magalhães Rocha; Thiago Pereira dos Santos; André De Gasperi; Daniel Galvão Carnier Fragoso; Gabriella Fazio; Ana Natalia Gomes Rodrigues (Marine and Petroleum Geology, 2023)

Magnetic signature and X-ray fluorescence for mapping trace elements in soils originating from basalt and sandstone - João de Deus Ferreira e Silva; José Marques Júnior; Luis Fernando Vieira da Silva; Angelina Pedro Chitlhango; Laércio Santos Silva; Daniel De Bortoli Teixeira; Mara Regina Moitinho; Kathleen Fernandes; Luis Reynaldo Ferracciú Alleoni (Chemosphere, 2023)

Integrating chemical and biological data by chemometrics to evaluate detoxification responses of a neotropical bivalve to metal and metalloid contamination - Iara da C. Souza; Mariana Morozesk; Vinicius C. Azevedo; Julieta Griboff; Michael Elliott; Silvia T. Matsumoto; Magdalena V. Monferrán; Daniel A. Wunderlin; Marisa N. Fernandes (Chemosphere, 2023)

WITHDRAWN: Marine intrusions drive short-term and long lasting changes on limnological dynamics along the water column of a tropical coastal lagoon - Jorge Gabriel Fernandes Genovez; Théo Dias Arueira; Luís Alfredo dos Santos Prado; Giovanna Figueiredo Lima da Silva; Claudio Cardoso Marinho; André Luiz dos Santos Fonseca; Murilo Minello; Daniel Basílio Zandonadi; Rodrigo Lemes Martins; Francisco de Assis Esteves; Anderson da Rocha Gripp (Limnologica, 2023)

Annotation of transposable elements in the transcriptome of the Neotropical brown stink bug Euschistus heros and its chromosomal distribution - Jaqueline Fernanda Dionisio; Larissa Forim Pezenti; Rogério Fernandes de Souza; Daniel Ricardo Sosa-Gómez; Renata da Rosa (Molecular Genetics and Genomics, 2023)

Associations of the consumption of unprocessed red meat and processed meat with the incidence of cardiovascular disease and mortality, and the dose-response relationship: A systematic review and meta-analysis of cohort studies - Gidyenne Christine Bandeira Silva de Medeiros; Gabriela Xavier Barbalho Mesquita; Severina Carla Vieira Cunha Lima; David Franciole de Oliveira Silva; Kesley Pablo Morais de Azevedo; Isac Davidson Santiago Fernandes Pimenta; Ana Katherine da Silveira Gonçalves de Oliveira; Clélia de Oliveira Lyra; Daniel Guillén Martínez; Grasiela Piuvezam (Critical Reviews in Food Science and Nutrition, 2023)

Microplastic in mangroves: A worldwide review of contamination in biotic and abiotic matrices - Dayene Santiago Mendes; Colin Robert Beasley; Daniel Nobre Nunes Silva; Marcus Emanuel Barroncas Fernandes (Marine Pollution Bulletin, 2023)

Optimization of system of Oscillating Water Columns to mitigate pitch response of FPSO platforms submitted to head waves - Daniel de Oliveira Costa; Antonio Carlos Fernandes; Joel Sena Sales Junior (Ocean Engineering, 2023)

Geochemistry and geochronology of the Imbicuí Complex, Western Dom Feliciano Belt, Brazil: Tonian adakite-like subduction-related rocks - Rosemeri Soares Siviero; Edinei Koester; Luis Alberto Dávila Fernandes; Delphine Bosch; Olivier Bruguier; Daniel Triboli Vieira; Rodrigo Chaves Ramos; Gustavo Kraemer (Journal of South American Earth Sciences, 2023)

Glomalin mediation of plant functional traits unveiled in an extreme ecosystem - Carla Rago; Daniel Negreiros; Yumi Oki; Dario C. Paiva; Vanessa M. Gomes; Simon Pierce; G. Wilson Fernandes (Flora, 2023)

Metalliferous atmospheric settleable particulate matter action on the fat snook fish (Centropomus parallelus): Metal bioaccumulation, antioxidant responses and histological changes in gills, hepatopancreas and kidneys. - Rafaella Monteiro; Iara da Costa Souza; Mariana Morozesk; Michelly Pereira Soares; Carolina Fernandes De Angelis; Nathan S. Vieira; Fabiano Bendhack; Magdalena Victoria Monferrán; Daniel Alberto Wunderlin; Marisa Narciso Fernandes (Chemosphere, 2023)

Settleable atmospheric particulate matter harms a marine invertebrate: Integrating chemical and biological damage in a bivalve model - Luis Felipe de Almeida Duarte; Andressa dos Santos Barbosa Ortega; Marina de Souza Paço; Helen Sadauskas-Henrique; Caio Cesar-Ribeiro; Iara Costa Souza; Rafaella Monteiro; Magdalena Victoria Monferrán; Daniel Alberto Wunderlin; Marisa Narciso Fernandes; Camilo Dias Seabra Pereira (Science of The Total Environment, 2023)

Aboveground biomass estimation in dry forest in northeastern Brazil using metrics extracted from sentinel-2 data: Comparing parametric and non-parametric estimation methods - Márcia Rodrigues de Moura Fernandes; Gilson Fernandes da Silva; André Quintão de Almeida; Milton Marques Fernandes; Adriano Ribeiro de Mendonça; Fabio Guimarães Gonçalves; Daniel Henrique Breda Binoti; Jeferson Pereira Martins Silva (Advances in Space Research, 2023)

Similar regional-scale survival of tropical and southern temperate birds from the New World - Leonardo Fernandes França; Clarisse Caroline de Oliveira e Silva; João Batista de Pinho; Nêmora Pauletti Prestes; Victor R. Cueto; Maria Alice S. Alves; Fabio Schunck; Carla Suertegaray Fontana; Camile Lugarini; Jaime Martinez; M. Cecilia Sagario; Javier Lopez de Casenave; et al. (Oecologia, 2023)

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

Thermal tolerance limits and physiological traits as indicators of Hediste diversicolor's acclimation capacity to global and local change drivers - Joana Filipa Fernandes; Ricardo Calado; Daniel Jerónimo; Diana Madeira (Journal of Thermal Biology, 2023)

Relationships between fluid mixing, biodiversity, and chemosynthetic primary productivity in Yellowstone hot springs - Maria C. Fernandes‐Martins; Daniel R. Colman; Eric S. Boyd (Environmental Microbiology, 2023)
The factors that influence biodiversity and productivity of hydrothermal ecosystems are not well understood. Here we investigate the relationship between fluid mixing, biodiversity, and chemosynthetic primary productivity in three co‐localized hot springs (RSW, RSN, and RSE) in Yellowstone National Park that have different geochemistry. All three springs are sourced by reduced hydrothermal fluid, but RSE and RSN receive input of vapour phase gas and oxidized groundwaters, with input of both being substantially higher in RSN. Metagenomic sequencing revealed that communities in RSN were more biodiverse than those of RSE and RSW in all dimensions evaluated. Microcosm activity assays indicate that rates of dissolved inorganic carbon (DIC) uptake were also higher in RSN than in RSE and RSW. Together, these results suggest that increased mixing of reduced volcanic fluid with oxidized fluids generates additional niche space capable of supporting increasingly biodiverse communities that are more productive. These results provide insight into the factors that generate and maintain chemosynthetic biodiversity in hydrothermal systems and that influence the distribution, abundance, and diversity of microbial life in communities supported by chemosynthesis. These factors may also extend to other ecosystems not supported by photosynthesis, including the vast subterranean biosphere and biospheres beneath ice sheets and glaciers.

Association of polar fraction of Ageratum conyzoides from the Brazilian Amazon with doxycycline against infection of macrophages with Ehrlichia canis - Carla Janaina Rebouças Marques do Rosário; Daniel Moura de Aguiar; Cristian Alex Aquino Lima; Denise Fernandes Coutinho; José Gomes Pereira; Ferdinan Almeida Melo; Claudia Quintino da Rocha (South African Journal of Botany, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Applicability of machine learning techniques in food intake assessment: A systematic review - Larissa Oliveira Chaves; Ana Luiza Gomes Domingos; Daniel Louzada Fernandes; Fabio Ribeiro Cerqueira; Rodrigo Siqueira-Batista; Josefina Bressan (Critical Reviews in Food Science and Nutrition, 2023)

Toxic plants from the perspective of a “Quilombola” community in the Cerrado region of Brazil - Ricardo de Castro Santos Paim; Luiza Gabriella Ferreira de Paula; Débora Moreira Soares; Tarik Fernandes Gonçalves Rocha; Amanda Lopes Ribeiro; Natália Barros; Fabrício Carrião dos Santos; Heleno Dias Ferreira; Vera Lúcia Gomes-Klein; Benito Soto-Blanco; José Paes de Oliveira-Filho; Paulo Henrique Jorge da Cunha; et al. (Toxicon, 2023)

Population dynamics and movements of Atlantic tarpon, Megalops atlanticus, in the Parnaíba Delta Protected Area, Brazil: challenges for local fishery management planning - Cezar A. F. Fernandes; Francisca E. A. Cunha; Carlos E. L. S. Silva; Alan C. S. Araújo; Rafael L. Pereira; Daniel F. Viana; Werlanne M. S. Magalhães; M. A. P. Gondolo; Daniel M. P. de Castro; Aaron Adams; Jiangang Luo; Jerald S. Ault; et al. (Environmental Biology of Fishes, 2023)

A multi-biomarker approach to assess the sublethal effects of settleable atmospheric particulate matter from an industrial area on Nile tilapia (Oreochromis niloticus) - Henrique Aio Adorno; Iara da Costa Souza; Magdalena Victoria Monferrán; Daniel Alberto Wunderlin; Marisa Narciso Fernandes; Diana Amaral Monteiro (Science of The Total Environment, 2023)

A review on the modeling of subsea lifting operations - Emerson Martins de Andrade; Daniel de Oliveira Costa; Antonio Carlos Fernandes; Joel Sena Sales Junior (Ocean Engineering, 2023)

Using low-cost sensors to assess real-time comfort and air quality patterns in indoor households - Johnny Reis; Diogo Lopes; Daniel Graça; Ana Patrícia Fernandes; Ana Isabel Miranda; Myriam Lopes (Environmental Science and Pollution Research, 2023)

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Ecstasy metabolites and monoamine neurotransmitters upshift the Na+/K+ ATPase activity in mouse brain synaptosomes - Daniel José Barbosa; João Paulo Capela; Luísa Maria Ferreira; Paula Sério Branco; Eduarda Fernandes; Maria de Lourdes Bastos; Félix Carvalho (Archives of Toxicology, 2022)

Transcriptome Analysis of Immune Response against Streptococcus agalactiae Infection in the Nile Tilapia GIFT Strain - Tao Zhou; Zhihua Fang; Daniel F. C. Duarte; Stefan A. Fernandes; Ying Lu; Jing Guo; Lang Gui; Liangbiao Chen (Fishes, 2022)
Streptococcus agalactiae (group B streptococcus, GBS), a broad-spectrum pathogen, causes great economic losses in fish aquaculture, especially the industry of tilapia. Until now, the knowledge of the immune response mechanism against S. agalactiae infection in tilapia has been limited. In the present study, the gill transcriptome of the tilapia from the GBS and the phosphate buffered saline (PBS) groups were sequenced. The transcriptomic analysis results presented the differentially expressed genes (DEGs) at different time points (DEGs number, 6 h: 2122, 9 h: 1851, 15 h: 1791, and 18 h: 2395) after GBS injection, and significantly enriched immune-related gene ontology (GO) terms such as the innate immune response. The significantly enriched immune pathways included the Toll-like receptor signaling pathway, the nucleotide oligomerization domain (NOD)-like receptor signaling pathway, the cytosolic-DNA sensing pathway, and the intestinal immune network for Immunoglobulin A (IgA) production. Most of the DEGs in Toll-like receptor signaling, NOD-like receptor signaling, and cytosolic-DNA sensing pathways presented upregulations at 18 h, which indicated that the innate immune pathways were activated. Two immune-related pathways (phagosome and cell adhesion molecules) were significantly enriched at all time points, suggesting that these two pathways might also play important roles in the immune response against the GBS infection. The results of HE staining showed that the gills of tilapia were damaged seriously at 9 h post-infection, which might be due to the possibility of pyroptosis resulting from the changes of DEGs in the NOD-like receptor signaling pathway. This study provided new insight into the mechanisms of gill damage in fish infected with S. agalactiae.

A fatal case of dengue hemorrhagic fever associated with dengue virus 4 (DENV-4) in Brazil: genomic and histopathological findings - Mariana Sequetin Cunha; Thaís de Moura Coletti; Juliana Mariotti Guerra; César Cliento Ponce; Natalia Coelho Couto Azevedo Fernandes; Rodrigo Albegaria Résio; Ingra Morales Claro; Flávia Salles; Daniel Ferreira Lima Neto; Ester Sabino (Brazilian Journal of Microbiology, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Acute oral toxicity, antinociceptive and antimicrobial activities of kava dried extracts and synthetic kavain - Juliana Veloso Ferreira; Isabella Campolina Pierotte; Felipe Fernandes Rodrigues; Larissa Camila Ribeiro de Souza; Rafael Wesley Bastos; Paulo Henrique Fonseca Carmo; Geovanni Dantas Cassali; Carlos Alberto Tagliati; Renes Resende Machado; Daniel Assis Santos; Gerson Antônio Pianetti; Isabela Costa César (Natural Product Research, 2022)

Soil mapping for precision agriculture using support vector machines combined with inverse distance weighting - Gustavo Willam Pereira; Domingos Sárvio Magalhães Valente; Daniel Marçal de Queiroz; Nerilson Terra Santos; Elpídio Inácio Fernandes-Filho (Precision Agriculture, 2022)

Thanatology in the northern muriqui (Brachyteles hypoxanthus) - Robério Freire Filho; Igor Inforzato; Fernanda P. Tabacow; Waldney Martins; Carla B. Possamai; Daniel Ferraz; Robson O. E. Hack; Samantha Rocha; Daniel V. Slomp; Marcello S. Nery; Letícia Almeida; Naíla Fernandes; et al. (Primates, 2022)

Leaching of Herbicides in Soil under the Influence of Different Rainfall Intensities - Jesley Nogueira Bandeira; Lucrecia Pacheco Batista; Paulo Sérgio Fernandes das Chagas; Tatiane Severo Silva; Bruno Caio Chaves Fernandes; Eunice Maia de Andrade; Daniel Valadão Silva (Water, Air, & Soil Pollution, 2022)

First records of Curarea (Menispermaceae) in Southeastern Brazil - Pablo Fernando Feliz; Thiago Fernandes; Carlos Daniel Miranda Ferreira; João Marcelo Alvarenga Braga (Kew Bulletin, 2022)

Reproductive biology and hybridization of Physalis L. species - André Dutra Silva Junior; André Ricardo Zeist; Daniel Fernandes da Silva; Murilo Henrique de Souza Leal; Guilherme José Almeida Oliveira; Joana Nascimento Merces de Oliveira; Khamis Youssef; Bruno Da Rocha Toroco (Brazilian Journal of Botany, 2022)

Which birds are Brazilians seeing on urban and non-urban feeders? An analysis based on a collective online birding - Eduardo Roberto Alexandrino; Thaís Abreu Camboim; Flávia Guimarães Chaves; Alex Augusto Abreu Bovo; Marco Aurélio Galvão da Silva; Daniela Alves Maia da Silva; Margi Moss; Tatiana Pongiluppi Souza; Clarissa de Oliveira Santos; Caio Bezerra de Mattos Brito; Maristela Camolesi Alcantara; Karlla V. C. Barbosa; et al. (Ornithology Research, 2022)

Subtle structures with not‐so‐subtle functions: A data set of arthropod constructs and their host plants - Cássio Cardoso Pereira; Samuel Novais; Milton Barbosa; Daniel Negreiros; Thiago Gonçalves‐Souza; Tomas Roslin; Robert Marquis; Nicholas Marino; Vojtech Novotny; Jerome Orivel; Shen Sui; Gustavo Aires; et al. (Ecology, 2022)
The construction of shelters on plants by arthropods might influence other organisms via changes in colonization, community richness, species composition, and functionality. Arthropods, including beetles, caterpillars, sawflies, spiders, and wasps often interact with host plants via the construction of shelters, building a variety of structures such as leaf ties, tents, rolls, and bags; leaf and stem galls, and hollowed out stems. Such constructs might have both an adaptive value in terms of protection (i.e., serve as shelters) but may also exert a strong influence on terrestrial community diversity in the engineered and neighboring hosts via colonization by secondary occupants. Although different traits of the host plant (e.g., physical, chemical, and architectural features) may affect the potential for ecosystem engineering by insects, such effects have been, to a certain degree, overlooked. Further analyses of how plant traits affect the occurrence of shelters may therefore enrich our understanding of the organizing principles of plant‐based communities. This data set includes more than 1000 unique records of ecosystem engineering by arthropods, in the form of structures built on plants. All records have been published in the literature, and span both natural structures (91% of the records) and structures artificially created by researchers (9% of the records). The data were gathered between 1932 and 2021, across more than 50 countries and several ecosystems, ranging from polar to tropical zones. In addition to data on host plants and engineers, we aggregated data on the type of constructs and the identity of inquilines using these structures. This data set highlights the importance of these subtle structures for the organization of terrestrial arthropod communities, enabling hypotheses testing in ecological studies addressing ecosystem engineering and facilitation mediated by constructs. There are no copyright restrictions and please cite this paper when using the data in publications.

Molecular genotyping reveals inter-regional relatedness among antimicrobial resistant Salmonella Minnesota strains isolated from poultry farm and humans, Brazil - João Paulo Fernandes Ferreira Moreira; Daniel Farias Marinho do Monte; Camila de Aguiar Lima; Celso José Bruno de Oliveira; Nelson Rodrigo da Silva Martins; Angelo Berchieri Junior; Oliveiro Caetano de Freitas Neto (Brazilian Journal of Microbiology, 2022)

Interaction between herbicides applied in mixtures alters the conception of its environmental impact - Tatiane Severo Silva; Rita de Cássia Araújo de Medeiros; Daniel Valadão Silva; Matheus de Freitas Souza; Paulo Sergio Fernandes das Chagas; Hamurábi Anizio Lins; Cydianne Cavalcante da Silva; Carolina Malala Martins Souza; Vander Mendonça (Environmental Science and Pollution Research, 2022)

Bioconcentration and toxicological impacts of fipronil and 2,4-D commercial formulations (single and in mixture) in the tropical fish, Danio rerio. - Natália Prudêncio Viana; Laís Conceição Menezes da Silva; Natália Portruneli; Michelly Pereira Soares; Israel Luz Cardoso; Rocío Inés Bonansea; Bianca Veloso Goulart; Cassiana Carolina Montagner; Evaldo Luiz Gaeta Espíndola; Daniel Alberto Wunderlin; Marisa Narciso Fernandes (Environmental Science and Pollution Research, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Rainfall and drainage basin shape strongly control temporal and spatial variation of dissolved organic matter in a tropical lake - Luciana Pena Mello Brandão; Peter Anton Staehr; Ludmila Silva Brighenti; Daniel Peifer; Francisco Antônio Rodrigues Barbosa; José Fernandes Bezerra-Neto (Limnology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Impact of copper sulfate on survival, behavior, midgut morphology, and antioxidant activity of Partamona helleri (Apidae: Meliponini) - Rodrigo Cupertino Bernardes; Kenner Morais Fernandes; Daniel Silva Sena Bastos; André Filipe Penha Aires Freire; Marcos Pereira Lopes; Leandro Licursi de Oliveira; Mara Garcia Tavares; Renan dos Santos Araújo; Gustavo Ferreira Martins (Environmental Science and Pollution Research, 2022)

Water quality evaluation and dissolved organic matter characterization of a tropical hypereutrophic reservoir and its streams treated with Phoslock® and microbial bioremediation Enzilimp® - Mariana Peifer Bezerra; Elisa Aguiar Porto Viana; Luciana Pena Mello Brandão; Daniel Frank McGinnis; José Fernandes Bezerra-Neto; Francisco Antônio Rodrigues Barbosa (Environmental Science and Pollution Research, 2022)

Immunomodulatory Effect of Bifidobacterium, Lactobacillus, and Streptococcus Strains of Paraprobiotics in Lipopolysaccharide-Stimulated Inflammatory Responses in RAW-264.7 Macrophages - Monique Michels; Gabriel Fernandes Alves Jesus; Ana Paula Lorenzen Voytena; Marina Rossetto; Fernanda Ramlov; Emily Córneo; Paulo Feuser; Daniel Gelain; Felipe Dal-Pizzol (Current Microbiology, 2022)

ZnO nanoparticles alter redox metabolism of Limnoperna fortunei - Francine Girardello; Camila Custódio Leite; Luciana Bavaresco Touguinha; Mariana Roesch-Ely; Chrys Katielli Hoinacki da Silva; Richard Macedo de Oliveira; Daniel Lazaro Gallindo Borges; Izabel Vianna Villela; Andreia Neves Fernandes; Mirian Salvador; João Antonio Pêgas Henriques (Environmental Science and Pollution Research, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Epigallocatechin gallate has antibacterial and antibiofilm activity in methicillin resistant and susceptible Staphylococcus aureus of different lineages in non-cytotoxic concentrations - Carina Knidel; Monalessa Fábia Pereira; Divan Henrique Fernandes Barcelos; Daniel Cláudio de Oliveira Gomes; Marco César Cunegundes Guimarães; Ricardo Pinto Schuenck (Natural Product Research, 2021)

Four challenges when conducting bibliometric reviews and how to deal with them - João Paulo Romanelli; Maria Carolina Pereira Gonçalves; Luís Fernando de Abreu Pestana; Jéssica Akemi Hitaka Soares; Raquel Stucchi Boschi; Daniel Fernandes Andrade (Environmental Science and Pollution Research, 2021)

Soil Quality Indicators in an Ultisol Subjected to Chiseling in a Sugarcane Crop Under Mechanized Management in Southeastern Brazil - Daniel Pereira Pinheiro; Nilvan Carvalho Melo; Carolina Fernandes (Sugar Tech, 2021)

Swimming Improves Memory and Antioxidant Defense in an Animal Model of Duchenne Muscular Dystrophy - Priscila Mantovani Nocetti; Adriano Alberti; Viviane Freiberger; Letícia Ventura; Leoberto Ricardo Grigollo; Cristina Salar Andreau; Rudy José Nodari Júnior; Daniel Fernandes Martins; Clarissa M. Comim (Molecular Neurobiology, 2021)

Metagenome-assembled genome of a Chitinophaga sp. and its potential in plant biomass degradation, as well of affiliated Pandoraea and Labrys species - Michelli Inácio Gonçalves Funnicelli; Daniel Guariz Pinheiro; Elisângela Soares Gomes-Pepe; Lucas Amoroso Lopes de Carvalho; João Carlos Campanharo; Camila Cesário Fernandes; Luciano Takeshi Kishi; Lúcia Maria Carareto Alves; Eliana Gertrudes de Macedo Lemos (World Journal of Microbiology and Biotechnology, 2021)

Deterministic and Stochastic Principles to Convert Discrete Water Quality Data into Continuous Time Series - Danieli Mara Ferreira; Marcelo Coelho; Cristovao Vicente Scapulatempo Fernandes; Eloy Kaviski; Daniel Henrique Marco Detzel (Water Resources Management, 2021)

Peripheral receptors and neuromediators involved in the antihyperalgesic effects of acupuncture: a state-of-the-art review - Maísa Maria Spagnol Trento; Ari Ojeda Ocampo Moré; Elisa Cristiana Winkelmann Duarte; Daniel Fernandes Martins (Pflügers Archiv - European Journal of Physiology, 2021)

Detection of fusariosis on black pepper plants using multispectral sensor - Daniel Dourado Lacastagneratte; Fernando da Silva Rocha; Maria de Fátima Gonçalves Fernandes; Maria de Fátima Silva Muniz; Hugo César Rodrigues Moreira Catão; Carlos Juliano Brant Albuquerque (Journal of Plant Diseases and Protection, 2021)

Sorption kinetics of sulfometuron-methyl in different Brazilian soils - Quésia Sá Pavão; Matheus de Freitas Souza; Hamurábi Anizio Lins; Paulo Sérgio Fernandes das Chagas; Tatiane Severo Silva; Ana Beatriz Rocha de Jesus Passos; Ruana Karoline Viana Pereira; Daniel Valadão Silva (Environmental Monitoring and Assessment, 2021)

Changes in the Physical, Mineralogical and Geomechanical Properties of a Granitic Rock from Weathering Zones in a Tropical Climate - Daniel Silva Jaques; Eduardo Antonio Gomes Marques; Lázaro Corrêa Marcellino; Márcio Fernandes Leão; Eduardo Pereira Silveira Ferreira; Carolina Crissafe dos Santos Lemos (Rock Mechanics and Rock Engineering, 2020)

Physicochemical characterization and in vitro biological evaluation of solid compounds from furazolidone-based cyclodextrins for use as leishmanicidal agents - Suzana Gonçalves Carvalho; Daniel Fernandes Cipriano; Jair Carlos Checon de Freitas; Miguel Ângelo Schettino Junior; Enrique Ronald Yapuchura Ocaris; Carolina Bioni Garcia Teles; Aurileya de Jesus Gouveia; Ricardo Pereira Rodrigues; Marcos Santos Zanini; Janaína Cecília Oliveira Villanova (Drug Delivery and Translational Research, 2020)

Positive response of seedlings from an old-growth grassland to soil quality improvement - Thaise de O. Bahia; Hernani A. Almeida; Milton Barbosa; Daniel Negreiros; Mauricio Quesada; G. Wilson Fernandes (Brazilian Journal of Botany, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Lipoic Acid and Fish Oil Combination Potentiates Neuroinflammation and Oxidative Stress Regulation and Prevents Cognitive Decline of Rats After Sepsis - Amanda Della Giustina; Mariana Pereira de Souza Goldim; Lucinéia Gainski Danielski; Leandro Garbossa; Aloir Neri Oliveira Junior; Thainá Cidreira; Taís Denicol; Sandra Bonfante; Naiana da Rosa; Jucélia Jeremias Fortunato; Juliete Palandi; Bruna Hoffmann de Oliveira; et al. (Molecular Neurobiology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Performance of precipitation products obtained from combinations of satellite and surface observations - José Roberto Rozante; Enver Ramirez Gutierrez; Alex de Almeida Fernandes; Daniel A. Vila (International Journal of Remote Sensing, 2020)

Effect of Aerobic Physical Exercise in an Animal Model of Duchenne Muscular Dystrophy - Andreza Hoepers; Adriano Alberti; Viviane Freiberger; Letícia Ventura; Leoberto Ricardo Grigollo; Cristina Salar Andreu; Bruna Becker da Silva; Daniel Fernandes Martins; Rudy José Nodari Junior; Emilio L. Streck; Clarissa M. Comim (Journal of Molecular Neuroscience, 2020)

Bright coloration of male blue manakin is not connected to higher rates of nest predation - Carlos Biagolini-Jr; Daniel Fernandes Perrella (acta ethologica, 2020)

Is it stochastic? Chaoborus larvae bioturbation likely affect the timing of daily methane (CH4) ebullitive flux in a tropical reservoir - Mariana Peifer Bezerra; Daniel Frank McGinnis; José Fernandes Bezerra-Neto; Francisco Antônio Rodrigues Barbosa (Hydrobiologia, 2020)

Longitudinal study of rotavirus C VP6 genotype I6 in diarrheic piglets up to 1 week old - Joice Elaine Teixeira Campanha; Flávia Possatti; Elis Lorenzetti; Daniel de Almeida Moraes; Alice Fernandes Alfieri; Amauri Alcindo Alfieri (Brazilian Journal of Microbiology, 2020)

First record of geophagy by a Ramphastidae species (Piciformes) - Bianca Santos Matinata; Daniel Fernandes Perrella (Ornithology Research, 2020)

Phenotypic characterization of recurrent selection S1 Papaya (Carica papaya L.) families by multivariate approach - Renato Santa-Catarina; Julio Cesar Fiorio Vettorazzi; Diego Fernando Marmolejo Cortes; Josefa Grasiela Silva Santana; Tathianne Pastana de Sousa Poltronieri; Daniel Pereira Miranda; Adriana Azevedo Vimercati Pirovani; Nádia Fernandes Moreira; Marcelo Vivas; Messias Gonzaga Pereira (Euphytica, 2020)

Analysis of Chemical Features of a Soil Used as Landfill: Using the X-Ray Fluorescence (XRF) Technique - Willian Fernando de Borba; José Luiz Silvério da Silva; Pedro Daniel da Cunha Kemerich; Éricklis Edson Boito de Souza; Gabriel D’ávila Fernandes; Ivan Ricardo Carvalho (Water, Air, & Soil Pollution, 2020)

Correction to: Ecological restoration as a strategy for mitigating and adapting to climate change: lessons and challenges from Brazil - Mercedes M. C. Bustamante; José Salomão Silva; Aldicir Scariot; Alexandre Bonesso Sampaio; Daniel Luis Mascia Vieira; Edenise Garcia; Edson Sano; Geraldo Wilson Fernandes; Giselda Durigan; Iris Roitman; Isabel Figueiredo; Ricardo Ribeiro Rodrigues; et al. (Mitigation and Adaptation Strategies for Global Change, 2020)

Influence of the Holocene relative sea level on the coastal plain of Sepetiba Bay (Southeast Brazil) - Maria Virgínia Alves Martins; Anita Fernandes Souza Pinto; Leonardo Borghi; Thiago Gonçalves Carelli; Maider Morlote; Daniel Rey; Egberto Pereira; José Carlos Martins Ramalho; Fernando Rocha; Mauro Geraldes; Guilherme Loriato Potratz; Wania Duleba; et al. (Journal of Sedimentary Environments, 2020)

The potential of nanobiopesticide based on zein nanoparticles and neem oil for enhanced control of agricultural pests - Mônica Pascoli; Felícia Pereira de Albuquerque; Anderson Kikuchi Calzavara; Bruno Tinoco-Nunes; Wanderson Henrique Cruz Oliveira; Kelly Cristina Gonçalves; Ricardo Antônio Polanczyk; Jaqueline Franciosi Della Vechia; Sidnéia Terezinha Soares de Matos; Daniel Júnior de Andrade; Halley Caixeta Oliveira; Jayme A. Souza-Neto; et al. (Journal of Pest Science, 2020)

Genome-wide association studies for growth traits in buffaloes using the single step genomic BLUP - Francisco Ribeiro de Araujo Neto; Daniel Jordan de Abreu Santos; Gerardo Alves Fernandes Júnior; Rusbel Raul Aspilcueta-Borquis; André Vieira do Nascimento; Leonardo de Oliveira Seno; Humberto Tonhati; Henrique Nunes de Oliveira (Journal of Applied Genetics, 2020)

Recent advances on magnetic biosorbents and their applications for water treatment - Sofia F. Soares; Tiago Fernandes; Tito Trindade; Ana L. Daniel-da-Silva (Environmental Chemistry Letters, 2020)

New lake in a changing world: the construction and filling of a small hydropower reservoir in the tropics (Rio de Janeiro, Brazil) - Christina Wyss Castelo Branco; João José Fonseca Leal; Vera Lúcia de Moraes Huszar; Daniel da Silva Farias; Tatiana Dillenbug Saint’Pierre; Izidro Ferreira Sousa-Filho; Elisabete Fernandes de Albuquerque de Palermo; Alcides Wagner Serpa Guarino; Adalto Rodrigues Gomes; Betina Kozlowsky-Suzuki (Environmental Science and Pollution Research, 2019)

Nanoformulation as a tool for improvement of thiamethoxam encapsulation and evaluation of ecotoxicological impacts - Marcia Regina Assalin; Lucas Daniel Lavansdoski dos Santos; Debora Renata Cassoli de Souza; Maria Aparecida Rosa; Rafaela Rangni Moltocaro Duarte; Rodrigo Fernandes Castanha; Patricia Pulcini Rosvald Donaire; Nelson Durán (Energy, Ecology and Environment, 2019)

Multivariate analysis and multiple linear regression as a tool to estimate the behavior of hexazinone in Brazilian soils - Luiz Odonil Gomes dos Santos; Matheus de Freitas Souza; Paulo Sergio Fernandes das Chagas; Taliane Maria Silva da Teófilo; Maria Alice Porto Formiga; Rita Cássia Araújo de Medeiros; Daniel Valadão Silva (Environmental Monitoring and Assessment, 2019)

Cadmium toxicity and its relationship with disturbances in the cytoskeleton, cell cycle and chromosome stability - Daniel Pizzaia; Marina Lima Nogueira; Mateus Mondin; Marcia Eugenia Amaral Carvalho; Fernando Angelo Piotto; Millor Fernandes Rosario; Ricardo Antunes Azevedo (Ecotoxicology, 2019)

Ecological restoration as a strategy for mitigating and adapting to climate change: lessons and challenges from Brazil - Mercedes M. C. Bustamante; José Salomão Silva; Aldicir Scariot; Alexandre Bonesso Sampaio; Daniel Luis Mascia; Edenise Garcia; Edson Sano; Geraldo Wilson Fernandes; Giselda Durigan; Iris Roitman; Isabel Figueiredo; Ricardo Ribeiro Rodrigues; et al. (Mitigation and Adaptation Strategies for Global Change, 2019)

Well-sampled regions risk loosing key biological data: a case study in the Atlantic Forest - Ravi Fernandes Mariano; Marco Aurélio Leite Fontes; Rubens Manoel dos Santos; Carolina Njaime Mendes; Aloysio Souza de Moura; Daniel Mendonça Torres; Leandro Bortoli de Freitas; Ana Carolina Maioli Campos Barbosa; Warley Augusto Caldas Carvalho (Biodiversity and Conservation, 2019)

Stretch–shortening cycle exercise produces acute and prolonged impairments on endurance performance: is the peripheral fatigue a single answer? - Marcos D. Silva-Cavalcante; Patrícia Guimaraes Couto; Rafael de Almeida Azevedo; Arthur Fernandes Gáspari; Daniel Boari Coelho; Adriano Eduardo Lima-Silva; Romulo Bertuzzi (European Journal of Applied Physiology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Uncertainty analysis in the detection of trends, cycles, and shifts in water resources time series - Marcelo Coelho; Cristovão Vicente Scapulatempo Fernandes; Daniel Henrique Marco Detzel (Water Resources Management, 2019)

Past and emerging topics related to electronic waste management: top countries, trends, and perspectives - Daniel Fernandes Andrade; João Paulo Romanelli; Edenir Rodrigues Pereira-Filho (Environmental Science and Pollution Research, 2019)

Arsenic exposure intensifies glycogen nephrosis in diabetic rats - Marcela Nascimento Sertorio; Ana Cláudia Ferreira Souza; Daniel Silva Sena Bastos; Felipe Couto Santos; Luiz Otávio Guimarães Ervilha; Kenner Morais Fernandes; Leandro Licursi de Oliveira; Mariana Machado-Neves (Environmental Science and Pollution Research, 2019)

Chemical composition and evaluation of antinociceptive activity of the essential oil of Stevia serrata Cav. from Guatemala - Daniel Luiz Reis Simas; Max Samuel Mérida-Reyes; Manuel Alejandro Muñoz-Wug; Millena Santos Cordeiro; Thais Biondino Sardella Giorno; Edwin Adolfo Taracena; Bessie Evelyn Oliva-Hernández; José Vicente Martínez-Arévalo; Patricia Dias Fernandes; Juan Francisco Pérez-Sabino; Antonio Jorge Ribeiro da Silva (Natural Product Research, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Prevalence of subclinical hypocalcemia in dairy cows in the Sousa city micro-region, Paraíba state - Daniel Cézar da Silva; Beatriz Dantas Fernandes; Jessica Monique dos Santos Lima; Gilderlândio Pinheiro Rodrigues; Déborah Lanne Barros Dias; Evaristo Jorge de Oliveira Souza; Miguel Arcanjo Moreira Filho (Tropical Animal Health and Production, 2019)

Catch and yield trends of the Portuguese purse seine fishery (2006-2018) - Diana Feijó; Ana Marçalo; Laura Wise; Tiago Bento; Jorge Barra; Mário Correira; Daniel Pinto; Rubén Lechuga; Inês Dias; Mónica Felício; David Dinis; Mónica Inácio; et al. (Frontiers in Marine Science, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Correction to: Electroacupuncture induces antihyperalgesic effect through endothelin-B receptor in the chronic phase of a mouse model of complex regional pain syndrome type I - Leidiane Mazzardo-Martins; Daiana Cristina Salm; Elisa C. Winkelmann-Duarte; Júlia Koerich Ferreira; Daniela Dero Lüdtke; Kamilla Pamplona Frech; Luiz Augusto Oliveira Belmonte; Verônica Vargas Horewicz; Anna Paula Piovezan; Francisco José Cidral-Filho; Ari Ojeda Ocampo Moré; Daniel Fernandes Martins (Pflügers Archiv - European Journal of Physiology, 2018)

Electroacupuncture induces antihyperalgesic effect through endothelin-B receptor in the chronic phase of a mouse model of complex regional pain syndrome type I - Leidiane Mazzardo-Martins; Daiana Cristina Salm; Elisa C. Winkelmann-Duarte; Júlia Koerich Ferreira; Daniela Dero Lüdtke; Kamilla Pamplona Frech; Luiz Augusto Oliveira Belmonte; Verônica Vargas Horewicz; Anna Paula Piovezan; Francisco José Cidral-Filho; Ari Ojeda Ocampo Moré; Daniel Fernandes Martins (Pflügers Archiv - European Journal of Physiology, 2018)

Persistence of picloram in soil with different vegetation managements - Ana Beatriz R. J. Passos; Matheus F. Souza; Daniel Valadão Silva; Douglas T. Saraiva; Antônio Alberto da Silva; José C. Zanuncio; Beatriz Fernandes Seia Gonçalves (Environmental Science and Pollution Research, 2018)

Proteomic identification and purification of seed proteins from native Amazonian species displaying antifungal activity - Márcio V. Ramos; Daniel Brito; Cléverson D. T. Freitas; José Francisco C. Gonçalves; Camila T. M. N. Porfirio; Marina D. P. Lobo; Ana Cristina O. Monteiro-Moreira; Luiz A. C. Souza; Andreia V. Fernandes (Planta, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Effect of simvastatin on sensorial, motor, and morphological parameters in sciatic nerve crush induced-neuropathic pain in rats - Claudia Rita Corso; Daniel Fernandes Martins; Stephanie Carvalho Borges; Olair Carlos Beltrame; José Ederaldo Queiroz Telles; Nilza Cristina Buttow; Maria Fernanda de Paula Werner (Inflammopharmacology, 2018)

Protective effect of grape or apple juices in bone tissue of rats exposed to cadmium: role of RUNX-2 and RANK/L expression - Pedro Luiz Menin Ruiz; Bianca Andrade Handan; Carolina Foot Gomes de Moura; Livia Ribeiro Assis; Kelly Rossetti Fernandes; Ana Claudia Muniz Renno; Daniel Araki Ribeiro (Environmental Science and Pollution Research, 2018)

Towards automation of glycomic profiling of complex biological materials - Archana Shubhakar; Poh-Choo Pang; Daryl L. Fernandes; Anne Dell; Daniel I. R. Spencer; Stuart M. Haslam (Glycoconjugate Journal, 2018)

Efficiency of multi-trait, indirect, and trait-assisted genomic selection for improvement of biomass sorghum - Samuel B. Fernandes; Kaio O. G. Dias; Daniel F. Ferreira; Patrick J. Brown (Theoretical and Applied Genetics, 2018)

Characteristics of meiofauna in extreme marine ecosystems: a review - Daniela Zeppilli; Daniel Leduc; Christophe Fontanier; Diego Fontaneto; Sandra Fuchs; Andrew J. Gooday; Aurélie Goineau; Jeroen Ingels; Viatcheslav N. Ivanenko; Reinhardt Møbjerg Kristensen; Ricardo Cardoso Neves; Nuria Sanchez; et al. (Marine Biodiversity, 2018)

Phylogenetic analysis of standard metabolic rate of snakes: a new proposal for the understanding of interspecific variation in feeding behavior - Daniel Rodrigues Stuginski; Carlos Arturo Navas; Fábio Cury de Barros; Agustín Camacho; José Eduardo Pereira Wilken Bicudo; Kathleen Fernandes Grego; José Eduardo de Carvalho (Journal of Comparative Physiology B, 2018)

Vegetation cover of Brazil in the last 21 ka: New insights into the Amazonian refugia and Pleistocenic arc hypotheses - Daniel M. Arruda; Carlos E. G. R. Schaefer; Rúbia S. Fonseca; Ricardo R. C. Solar; Elpídio I. Fernandes‐Filho (Global Ecology and Biogeography, 2018)
Aim The two main hypotheses about the Neotropical palaeovegetation, namely that of Amazonian refugia by Haffer and of the Pleistocene arc by Prado and Gibbs, are still constantly debated. We offer new insights on this debate using ecological niche modelling with combined climate–soil predictors to test both hypotheses, reconstruct the palaeovegetation of the Last Glacial Maximum (LGM; 21 ka) and Mid‐Holocene (Mid‐H; 6 ka) and indicate the configuration of refugia areas. Location Brazil. Time period Last 21 ka. Major taxa studied Biomes. Methods We modelled the environmental space of the 10 most representative biomes with the RandomForest classifier, using climate predictors from three atmospheric general circulation models (CCSM4, MPI‐ESM‐P and MIROC‐ESM) and soil predictors, the same for the different situations. Based on the consensus among the models, we reconstructed the palaeovegetation cover for LGM and Mid‐H and used fossil pollen sites to validate the reconstructions in a direct comparison. Results The climate in the past was cooler and wetter throughout most of the territory. The Amazon basin region was the most affected by climate change in the last 21 ka, with equatorial rain forest retracting to refugia areas, while the tropical rain forest (with climatic preferences similar to the Atlantic forest) expanded in the basin. In southern Brazil, the mixed forest ( Araucaria forest) shifted to lower latitudes, while the grasslands expanded. In most biomes, the greatest changes occurred in the ecotonal zones, supported by pollen fossils. Main conclusions With regard to Haffer's hypothesis, the forests of the Amazonian lowlands retreated to refugia areas, while the colder and wetter climate of the basin created a favourable niche for another type of forest, instead of savanna. The advance of dry vegetation was restricted to ecotonal conditions, preventing the formation of a continuous Pleistocene arc, predicted by Prado and Gibbs's hypothesis.

Integrated ecological–economic fisheries models—Evaluation, review and challenges for implementation - J Rasmus Nielsen; Eric Thunberg; Daniel S Holland; Jorn O Schmidt; Elizabeth A Fulton; Francois Bastardie; Andre E Punt; Icarus Allen; Heleen Bartelings; Michel Bertignac; Eckhard Bethke; Sieme Bossier; et al. (Fish and Fisheries, 2018)
Marine ecosystems evolve under many interconnected and area‐specific pressures. To fulfil society's intensifying and diversifying needs while ensuring ecologically sustainable development, more effective marine spatial planning and broader‐scope management of marine resources is necessary. Integrated ecological–economic fisheries models ( IEEFM s) of marine systems are needed to evaluate impacts and sustainability of potential management actions and understand, and anticipate ecological, economic and social dynamics at a range of scales from local to national and regional. To make these models most effective, it is important to determine how model characteristics and methods of communicating results influence the model implementation, the nature of the advice that can be provided and the impact on decisions taken by managers. This article presents a global review and comparative evaluation of 35 IEEFM s applied to marine fisheries and marine ecosystem resources to identify the characteristics that determine their usefulness, effectiveness and implementation. The focus is on fully integrated models that allow for feedbacks between ecological and human processes although not all the models reviewed achieve that. Modellers must invest more time to make models user friendly and to participate in management fora where models and model results can be explained and discussed. Such involvement is beneficial to all parties, leading to improvement of mo‐dels and more effective implementation of advice, but demands substantial resources which must be built into the governance process. It takes time to develop effective processes for using IEEFM s requiring a long‐term commitment to integrating multidisciplinary modelling advice into management decision‐making.

Exposure to predicted precipitation patterns decreases population size and alters community structure of cyanobacteria in biological soil crusts from the Chihuahuan Desert - Vanessa M.C. Fernandes; Náthali Maria Machado de Lima; Daniel Roush; Jennifer Rudgers; Scott L. Collins; Ferran Garcia‐Pichel (Environmental Microbiology, 2018)
Summary Cyanobacteria typically colonize the surface of arid soils, building biological soil crust (biocrusts) that provide a variety of ecosystem benefits, ranging from fertilization to stabilization against erosion. We investigated how future scenarios in precipitation anticipated for the Northern Chihuahuan Desert affected abundance and composition of biocrust cyanobacteria in two grassland ecosystems. Scenarios included a decrease in precipitation and a delay of monsoon rainfall. After three years, both treatments negatively affected cyanobacteria, although the effects of monsoon delay were milder than those of decreased precipitation. Mature biocrusts in black grama grassland suffered severe losses in cyanobacterial biomass and diversity, but compositionally simpler biocrusts in blue grama‐dominated grassland maintained biomass, only suffering diversity losses. This could be partially explained by the differential sensitivity of cyanobacterial taxa: nitrogen‐fixing Scytonema spp. were the most sensitive, followed by phylotypes in the Microcoleus steenstrupii complex. Microcoleus vaginatus was the least affected in all cases, but is known to be very sensitive to warming. We predict that altered precipitation will tend to prevent biocrusts from reaching successional maturity, selecting for M. vaginatus over competing M. steenstrupii , among pioneer biocrust‐formers. A shift towards heat‐sensitive M. vaginatus could ultimately destabilize biocrusts when precipitation changes are combined with global warming.

Facilitative effects of tree species on natural regeneration in an endangered biodiversity hotspot - Cristiani Spadeto; G. Wilson Fernandes; Daniel Negreiros; Sustanis Horn Kunz (Brazilian Journal of Botany, 2017)

Climate change impacts in Latin America and the Caribbean and their implications for development - Christopher P.O. Reyer; Sophie Adams; Torsten Albrecht; Florent Baarsch; Alice Boit; Nella Canales Trujillo; Matti Cartsburg; Dim Coumou; Alexander Eden; Erick Fernandes; Fanny Langerwisch; Rachel Marcus; et al. (Regional Environmental Change, 2017)

Sediments as a sink for UV filters and benzotriazoles: the case study of Upper Iguaçu watershed, Curitiba (Brazil) - Alinne Mizukawa; Daniel Molins-Delgado; Júlio César Rodrigues de Azevedo; Cristóvão Vicente Scapulatempo Fernandes; Silvia Díaz-Cruz; Damià Barceló (Environmental Science and Pollution Research, 2017)

Combining climatic and soil properties better predicts covers of Brazilian biomes - Daniel M. Arruda; Elpídio I. Fernandes-Filho; Ricardo R. C. Solar; Carlos E. G. R. Schaefer (The Science of Nature, 2017)

Ancient DNA reveals differences in behaviour and sociality between brown bears and extinct cave bears - Gloria G. Fortes; Aurora Grandal‐d'Anglade; Ben Kolbe; Daniel Fernandes; Ioana N. Meleg; Ana García‐Vázquez; Ana C. Pinto‐Llona; Silviu Constantin; Trino J. de Torres; Jose E. Ortiz; Christine Frischauf; Gernot Rabeder; et al. (Molecular Ecology, 2016)
Ancient DNA studies have revolutionized the study of extinct species and populations, providing insights on phylogeny, phylogeography, admixture and demographic history. However, inferences on behaviour and sociality have been far less frequent. Here, we investigate the complete mitochondrial genomes of extinct Late Pleistocene cave bears and middle Holocene brown bears that each inhabited multiple geographically proximate caves in northern Spain. In cave bears, we find that, although most caves were occupied simultaneously, each cave almost exclusively contains a unique lineage of closely related haplotypes. This remarkable pattern suggests extreme fidelity to their birth site in cave bears, best described as homing behaviour, and that cave bears formed stable maternal social groups at least for hibernation. In contrast, brown bears do not show any strong association of mitochondrial lineage and cave, suggesting that these two closely related species differed in aspects of their behaviour and sociality. This difference is likely to have contributed to cave bear extinction, which occurred at a time in which competition for caves between bears and humans was likely intense and the ability to rapidly colonize new hibernation sites would have been crucial for the survival of a species so dependent on caves for hibernation as cave bears. Our study demonstrates the potential of ancient DNA to uncover patterns of behaviour and sociality in ancient species and populations, even those that went extinct many tens of thousands of years ago.

Land use change (LUC) analysis and life cycle assessment (LCA) of Brazilian soybean biodiesel - Victor Paulo Peçanha Esteves; Elisa Maria Mano Esteves; Davi José Bungenstab; Daniel Gomes dos Santos Wendriner Loebmann; Daniel de Castro Victoria; Luiz Eduardo Vicente; Ofélia de Queiroz Fernandes Araújo; Cláudia do Rosário Vaz Morgado (Clean Technologies and Environmental Policy, 2016)

The skull of Hydrodynastes gigas (Duméril, Bibron & Duméril, 1854) (Serpentes: Dipsadidae) as a model of snake ontogenetic allometry inferred by geometric morphometrics - Roberta A. Murta-Fonseca; Daniel S. Fernandes (Zoomorphology, 2016)

Ecology and evolution of plant diversity in the endangered campo rupestre: a neglected conservation priority - Fernando A. O. Silveira; Daniel Negreiros; Newton P. U. Barbosa; Elise Buisson; Flávio F. Carmo; Daniel W. Carstensen; Abel A. Conceição; Tatiana G. Cornelissen; Lívia Echternacht; G. Wilson Fernandes; Queila S. Garcia; Tadeu J. Guerra; et al. (Plant and Soil, 2016)

Enrichment of Food Mixtures with Essential Fatty Acids and Calcium from Nile Tilapia By-Products - Márcia Fernandes Nishiyama; Aloisio Henrique Pereira de Souza; Hevelyse Munise Celestino dos Santos; Aline Kirie Gohara; Wilson Massamitu Furuya; Lauro Daniel Vargas Mendez; Ricardo Pereira Ribeiro; Makoto Matsushita (Journal of Aquatic Food Product Technology, 2016)

Efficiency of different hormonal treatments for estrus synchronization in tropical Santa Inês sheep - Tarcísio Alves Texeira; Jeferson Ferreira da Fonseca; Joanna Maria Gonçalves de Souza-Fabjan; Luciano de Rezende Carvalheira; Daniel Andrews de Moura Fernandes; Felipe Zandonadi Brandão (Tropical Animal Health and Production, 2016)

Is the meiofauna a good indicator for climate change and anthropogenic impacts? - Daniela Zeppilli; Jozée Sarrazin; Daniel Leduc; Pedro Martinez Arbizu; Diego Fontaneto; Christophe Fontanier; Andrew J. Gooday; Reinhardt Møbjerg Kristensen; Viatcheslav N. Ivanenko; Martin V. Sørensen; Ann Vanreusel; Julien Thébault; et al. (Marine Biodiversity, 2015)

Functional ecology as a missing link for conservation of a resource-limited flora in the Atlantic forest - Luiza F. A. de Paula; Daniel Negreiros; Luísa O. Azevedo; Renato L. Fernandes; João Renato Stehmann; Fernando A. O. Silveira (Biodiversity and Conservation, 2015)

Insights into the structure–activity relationships of chiral 1,2-diaminophenylalkane platinum(II) anticancer derivatives - Gilles Berger; Luca Fusaro; Michel Luhmer; Joanna Czapla-Masztafiak; Ewelina Lipiec; Jakub Szlachetko; Yves Kayser; Daniel L. A. Fernandes; Jacinto Sá; François Dufrasne; Sophie Bombard (JBIC Journal of Biological Inorganic Chemistry, 2015)

Environmental control of seed dormancy and germination of Mimosa calodendron (Fabaceae): implications for ecological restoration of a highly threatened environment - Roberta Lima Campos Dayrell; Silmary de Jesus Gonçalves-Alvim; Daniel Negreiros; G. Wilson Fernandes; Fernando Augusto Oliveira Silveira (Brazilian Journal of Botany, 2015)

Prevalence and risk factors associated with bovine genital campylobacteriosis and bovine trichomonosis in the state of Pernambuco, Brazil - Júnior Mário Baltazar de Oliveira; Gesika Maria da Silva; Antônio Fernando Barbosa Batista Filho; Jonas de Melo Borges; Pollyanne Raysa Fernandes de Oliveira; Daniel Friguglietti Brandespim; Rinaldo Aparecido Mota; José Wilton Pinheiro (Tropical Animal Health and Production, 2015)

Metal bioavailability and toxicity in freshwaters - Danielly de Paiva Magalhães; Mônica Regina da Costa Marques; Darcilio Fernandes Baptista; Daniel Forsin Buss (Environmental Chemistry Letters, 2015)

The ecophysiological performance of Vernonia polyanthes Less. (Asteraceae) in conserved and degraded forests in the Brazilian Cerrado - Daniel Baron; Diego da Silva Graciano; Roberto de Oliveira Portella; Luís Paulo Benetti Mantoan; Luiz Fernando Rolim de Almeida; Carmen Sílvia Fernandes Boaro (Acta Physiologiae Plantarum, 2015)

Insights into the mechanisms underlying the antiproliferative potential of a Co(II) coordination compound bearing 1,10-phenanthroline-5,6-dione: DNA and protein interaction studies - Daniel V. Luís; Joana Silva; Ana Isabel Tomaz; Rodrigo F. M. de Almeida; Miguel Larguinho; Pedro V. Baptista; Luísa M. D. R. S. Martins; Telma F. S. Silva; Pedro M. Borralho; Cecília M. P. Rodrigues; António S. Rodrigues; Armando J. L. Pombeiro; et al. (JBIC Journal of Biological Inorganic Chemistry, 2014)

MDMA impairs mitochondrial neuronal trafficking in a Tau- and Mitofusin2/Drp1-dependent manner - Daniel José Barbosa; Román Serrat; Serena Mirra; Martí Quevedo; Elena Gómez de Barreda; Jesús Ávila; Eduarda Fernandes; Maria de Lourdes Bastos; João Paulo Capela; Félix Carvalho; Eduardo Soriano (Archives of Toxicology, 2014)

CSR analysis of plant functional types in highly diverse tropical grasslands of harsh environments - Daniel Negreiros; Soizig Le Stradic; G. Wilson Fernandes; Henrique C. Rennó (Plant Ecology, 2014)

Adaptive plasticity of Laguncularia racemosa in response to different environmental conditions: integrating chemical and biological data by chemometrics - Iara da Souza; Marina Marques Bonomo; Mariana Morozesk; Lívia Dorsch Rocha; Ian Drumond Duarte; Larissa Maria Furlan; Hiulana Pereira Arrivabene; Magdalena Victoria Monferrán; Silvia Tamie Matsumoto; Camilla Rozindo Dias Milanez; Daniel Alberto Wunderlin; Marisa Narciso Fernandes (Ecotoxicology, 2014)

Bacterial pathogens, virulence mechanism and host defence in marine macroalgae - Suhelen Egan; Neil Daniel Fernandes; Vipra Kumar; Melissa Gardiner; Torsten Thomas (Environmental Microbiology, 2014)
Summary Macroalgae are important ecosystem engineers in temperate marine waters. The function of macroalgae is intimately linked to the composition and structure of their epibiotic bacterial, communities, and evidence has emerged that bacteria can also have a negative impact on their host by causing disease. A few examples exist where bacteria have been unambiguously linked to macroalgal disease, however in many cases, pathogenicity has not been clearly separated from saprophytic behaviour or secondary colonization after disease initiation. Nevertheless, pathogenic pressure by bacteria might be substantial, as macroalgae have evolved a range of innate and induced defence mechanism that have the potential to control bacterial attacks. The presence and abundance of virulence factors in marine bacteria, which have not previously been recognized as pathogens, also represents an underappreciated, opportunistic potential for disease. Given that virulence expression in opportunistic pathogens is often dependent on environmental conditions, we predict that current and future anthropogenic changes in the marine environment will lead to an increase in the occurrence of macroalgal disease. This review highlights important areas of research that require future attention to understand the link between environmental change, opportunistic pathogens and macroalgal health in the world's oceans.

ABO blood group polymorphisms and risk for ischemic stroke and peripheral arterial disease - Adriano de Paula Sabino; Daniel Dias Ribeiro; Caroline Pereira Domingheti; Danyelle Romana Alves Rios; Luci Maria SantAna Dusse; Maria das Graças Carvalho; Ana Paula Fernandes (Molecular Biology Reports, 2014)

"Ecstasy"-induced toxicity in SH-SY5Y differentiated cells: role of hyperthermia and metabolites - Daniel José Barbosa; João Paulo Capela; Renata Silva; Luísa Maria Ferreira; Paula Sério Branco; Eduarda Fernandes; Maria Lourdes Bastos; Félix Carvalho (Archives of Toxicology, 2014)

The mixture of “ecstasy” and its metabolites is toxic to human SH-SY5Y differentiated cells at in vivo relevant concentrations - Daniel José Barbosa; João Paulo Capela; Renata Silva; Vânia Vilas-Boas; Luísa Maria Ferreira; Paula Sério Branco; Eduarda Fernandes; Maria de Lourdes Bastos; Félix Carvalho (Archives of Toxicology, 2014)

Genetic diversity of porcine sapoviruses in pigs from the Amazon region of Brazil - Juliana das Merces Hernandez; Daniel Camargo Stangarlin; Jones Anderson Monteiro Siqueira; Darleise de Souza Oliveira; Thayara Morais Portal; Aline Fernandes Barry; Fabrício Aleixo Dias; Jane Cecilia Silveira de Matos; Joana D’Arc Pereira Mascarenhas; Yvone Benchimol Gabbay (Archives of Virology, 2013)

Neurobehavioral and genotoxic evaluation of (−)-linalool in mice - Vanessa Coelho; Leidiane Mazzardo-Martins; Daniel Fernandes Martins; Adair Roberto Soares Santos; Lucimar Filot da Silva Brum; Jaqueline Nascimento Picada; Patrícia Pereira (Journal of Natural Medicines, 2013)

Onset of sexual maturity and relative growth of the freshwater crab Trichodactylus fluviatilis (Trichodactyloidea) in south-eastern Brazil - Daniel José Marcondes Lima; Valter José Cobo; Douglas Fernandes Rodrigues Alves; Samara de Paiva Barros-Alves; Vivian Fransozo (Invertebrate Reproduction & Development, 2013)

Digestive enzyme activity in juvenile Nile tilapia (Oreochromis niloticus, L) submitted to different dietary levels of shrimp protein hydrolysate - Juliana Ferreira Santos; Patrícia Fernandes Castro; Albino Luciani Gonçalves Leal; Augusto Cézar Vasconcelos de Freitas Júnior; Daniel Lemos; Luiz Bezerra Carvalho; Ranilson Souza Bezerra (Aquaculture International, 2013)

Nandrolone Decanoate Induces Genetic Damage in Multiple Organs of Rats - Renan Pozzi; Kelly Rosseti Fernandes; Carolina Foot Gomes de Moura; Raquel Agnelli Mesquita Ferrari; Kristianne Porta Santos Fernandes; Ana Claudia Muniz Renno; Daniel Araki Ribeiro (Archives of Environmental Contamination and Toxicology, 2013)

Evaluation of Vulnerability to Extreme Climatic Events in the Brazilian Amazonia: Methodological Proposal to the Rio Acre Basin - José Antônio Sena; Marcos Aurélio V. Freitas; Daniel de Berrêdo; Lazaro Costa Fernandes (Water Resources Management, 2012)

−1131T>C and SW19 polymorphisms in APOA5 gene and lipid levels in type 2 diabetic patients - Mirelle O. Sóter; Karina B. Gomes; Ana P. Fernandes; Maria das G. Carvalho; Poliana S. Pinheiro; Adriana A. Bosco; Daniel D. R. Silva; Marinez O. Sousa (Molecular Biology Reports, 2012)

Analysis of Individual Versus Group Behavior of Zebrafish: a Model Using pH Sublethal Effects - Danielly de Paiva Magalhães; Daniel Forsin Buss; Rodolfo Armando da Cunha; Ana Rosa Linde-Arias; Darcilio Fernandes Baptista (Bulletin of Environmental Contamination and Toxicology, 2012)

Ecological implications on the aggregation of Amblyomma fuscum (Acari: Ixodidae) on Thrichomys laurentius (Rodentia: Echimyidae), in northeastern Brazil - Filipe Martins Aléssio; Filipe Dantas-Torres; Daniel Barreto Siqueira; Marie-Hélène Lizée; Maria Fernanda Vianna Marvulo; Thiago Fernandes Martins; Marcelo Bahia Labruna; Jean Carlos Ramos Silva; Jean-François Mauffrey (Experimental and Applied Acarology, 2012)

Identification of senescence and death in Emiliania huxleyi and Thalassiosira pseudonana : Cell staining, chlorophyll alterations, and dimethylsulfoniopropionate (DMSP) metabolism - Daniel J. Franklin; Ruth L. Airs; Michelle Fernandes; Thomas G. Bell; Roy J. Bongaerts; John A. Berges; Gill Malin (Limnology and Oceanography, 2012)
We measured membrane permeability, hydrolytic enzyme, and caspase‐like activities using fluorescent cell stains to document changes caused by nutrient exhaustion in the coccolithophore Emiliania huxleyi and the diatom Thalassiosira pseudonana , during batch‐culture nutrient limitation. We related these changes to cell death, pigment alteration, and concentrations of dimethylsulfide (DMS) and dimethylsulfoniopropionate (DMSP) to assess the transformation of these compounds as cell physiological condition changes. E. huxleyi persisted for 1 month in stationary phase; in contrast, T. pseudonana cells rapidly declined within 10 d of nutrient depletion. T. pseudonana progressively lost membrane integrity and the ability to metabolize 5‐chloromethylfluorescein diacetate (CMFDA; hydrolytic activity), whereas E. huxleyi developed two distinct CMFDA populations and retained membrane integrity (SYTOX Green). Caspase‐like activity appeared higher in E. huxleyi than in T. pseudonana during the post‐growth phase, despite a lack of apparent mortality and cell lysis. Photosynthetic pigment degradation and transformation occurred in both species after growth; chlorophyll a (Chl a ) degradation was characterized by an increase in the ratio of methoxy Chl a : Chl a in T. pseudonana but not in E. huxleyi , and the increase in this ratio preceded loss of membrane integrity. Total DMSP declined in T. pseudonana during cell death and DMS increased. In contrast, and in the absence of cell death, total DMSP and DMS increased in E. huxleyi . Our data show a novel chlorophyll alteration product associated with T. pseudonana death, suggesting a promising approach to discriminate nonviable cells in nature.

Plasminogen activator inhibitor-1 4G/5G promoter polymorphism and PAI-1 plasma levels in young patients with ischemic stroke - Adriano de Paula Sabino; Daniel Dias Ribeiro; Caroline Pereira Domingueti; Mariana Silva dos Santos; Telma Gadelha; Luci Maria SantAna Dusse; Maria das Graças Carvalho; Ana Paula Fernandes (Molecular Biology Reports, 2011)

Early-life environmental intervention may increase the number of neurons, astrocytes, and cellular proliferation in the hippocampus of rats - Elisa C. Winkelmann-Duarte; Camila B. Padilha-Hoffmann; Daniel F. Martins; Artur F. S. Schuh; Marilda C. Fernandes; Ricardo Santin; Suelen Merlo; Gilberto L. Sanvitto; Aldo B. Lucion (Experimental Brain Research, 2011)

Copper incorporation into recombinant CotA laccase from Bacillus subtilis: characterization of fully copper loaded enzymes - Paulo Durão; Zhenjia Chen; André T. Fernandes; Peter Hildebrandt; Daniel H. Murgida; Smilja Todorovic; Manuela M. Pereira; Eduardo P. Melo; Lígia O. Martins (JBIC Journal of Biological Inorganic Chemistry, 2008)

Behavioral response of Zebrafish Danio rerio Hamilton 1822 to sublethal stress by sodium hypochlorite: ecotoxicological assay using an image analysis biomonitoring system - Danielly de Paiva Magalhães; Rodolfo Armando da Cunha; José Augusto Albuquerque dos Santos; Daniel Forsin Buss; Darcílio Fernandes Baptista (Ecotoxicology, 2007)

Molecular characterization of the env gene from Brazilian field isolates of Bovine Leukemia Virus - Marcelo Fernandes Camargos; Ariel Pereda; Daniel Stancek; Maurílio Andrade Rocha; Jenner Karlisson Pimenta dos Reis; Irene Greiser-Wilke; Rômulo Cerqueira Leite (Virus Genes, 2007)

Genetic Diversity in South American Colletotrichum gloeosporioides Isolates from Stylosanthes guianensis, a Tropical Forage Legume - Segenet Kelemu; Daniel Z. Skinner; Jorge L. Badel; Claudia X. Moreno; María X. Rodríguez; Celso D. Fernandes; María J. Charchar; Sukumar Chakraborty (European Journal of Plant Pathology, 1999)